Organic EL display device

By using a specific resin composition and controlling the content of metal elements and halogen elements, the problem of insufficient production rhythm and reliability of the organic EL display device is solved, and a high sensitivity and stable pixel segmentation layer is achieved, which improves the luminous brightness and device reliability.

CN119836863APending Publication Date: 2025-04-15TORAY INDUSTRIES INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380064791.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-16
Filing Date
2023-07-25
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In the prior art, organic EL display devices have shortcomings in production beat shortening and reliability, especially the reduction in luminous brightness and non-lighting problems caused by pixel shrinkage. The application of high-sensitivity resin compositions is still not ideal.

Method used

A resin composition containing a resin having an alkali-soluble group protected by an acid detachable protective group and a photoacid generator is used to form a planarization layer and a pixel-dividing layer through exposure development and curing, and the content of metal elements and halogen elements is controlled within a specific range, thereby improving the sensitivity and reliability of the resin composition.

Benefits of technology

It achieves shortening the production beat and improving the reliability of the organic EL display device, suppressing pixel shrinkage, and improving luminous brightness and device stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119836863A_ABST
    Figure CN119836863A_ABST
Patent Text Reader

Abstract

The present invention addresses the problem of providing an organic EL display device having high sensitivity and excellent reliability, and provides an organic EL display device having at least a substrate, a first electrode, a second electrode, a light-emitting layer, a planarization layer, and a pixel division layer, the planarization layer or the pixel division layer has a cured product obtained by exposing, developing, and curing the following resin composition A or resin composition B. The resin composition A contains (A-1) a resin having an alkali-soluble group protected by a protective group that can be removed by an acid, and (B) a resin composition of a photoacid generator. [Resin Composition B] A resin composition containing a resin having an alkali-soluble group, (A-2) a compound having an alkali-soluble group protected by a protecting group that can be desorbed by an acid, and (B) a photoacid generator. The total content of a metal element and a halogen element in a cured product measured by time-of-flight secondary ion mass spectrometry is 1.0 * 1016 atom / cm < 3 > to 1.0 * 1023 atom / cm < 3 > inclusive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an organic EL display device. Background Art

[0002] Positive photosensitive resin compositions containing polyimide, polybenzoxazole, etc. have been widely used in surface protection layers, interlayer insulating films, planarization layers, etc. of semiconductor elements. Recently, they have been used in, for example, pixel segmentation layers of organic EL elements, planarization layers of thin film transistor (hereinafter referred to as "TFT") substrates, etc.

[0003] When a positive photosensitive resin composition containing polyimide or polybenzoxazole is used for a pixel segmentation layer of an organic EL element, the coating of the photosensitive resin composition is mostly carried out by coating based on a slit coater. In recent years, in order to increase production, the substrate is being enlarged and the wiring is complicated, and it is required to shorten the exposure time in the exposure process that has a great impact on the production cycle, that is, to increase the sensitivity of the photosensitive resin composition. Therefore, a display device using a highly sensitive positive photosensitive resin composition is proposed (for example, Patent Document 1).

[0004] On the other hand, in an organic pigment dispersion type color filter, it is known that the voltage drop of a liquid crystal display element can be suppressed by suppressing the amount of sodium or the total amount of sodium and potassium contained in a pixel to a low level (for example, Patent Document 2).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2022-34533

[0008] Patent Document 2: Japanese Patent Application Laid-Open No. 7-198928 Summary of the invention

[0009] Problems to be solved by the invention

[0010] Generally, in an organic EL (electro-luminescence) display device, an insulating layer called a pixel dividing layer is formed between a first electrode and a second electrode to divide pixels, and a planarization layer is formed on a TFT. In order to shorten the production cycle in an organic EL display device, it is effective to use a high-sensitivity resin composition, and a high-sensitivity resin composition has been developed.

[0011] On the other hand, in recent years, a phenomenon called pixel shrinkage (luminous brightness decreases from the ends of a pixel or a portion of a lit pixel becomes non-lit) has occurred in organic EL display devices, and higher reliability in suppressing pixel shrinkage has been required.

[0012] Even if the resin composition described in Patent Document 1 or 2 is applied to a pixel segmentation layer or a planarization layer of an organic EL display device, there is still a problem of insufficient reliability and sensitivity. Therefore, an object of the present invention is to provide an organic EL display device having high sensitivity and excellent reliability.

[0013] Means for solving problems

[0014] In order to achieve the above-mentioned object, the present invention adopts the following configuration.

[0015] An organic EL display device comprising at least a substrate, a first electrode, a second electrode, a light-emitting layer, a planarization layer, and a pixel division layer.

[0016] The planarization layer or the pixel division layer has a cured product obtained by exposing, developing, and curing the following resin composition A or resin composition B:

[0017] [Resin composition A] A resin composition comprising (A-1) a resin having an alkali-soluble group protected by a protecting group that can be removed by acid and (B) a photoacid generator,

[0018] [Resin composition B] A resin composition comprising a resin having an alkali-soluble group, (A-2) a compound having an alkali-soluble group protected by a protecting group that can be removed by an acid, and (B) a photoacid generator,

[0019] The total content of metal elements and halogen elements in the cured product measured by time-of-flight secondary ion mass spectrometry was 1.0×10 16 atom / cm 3 Above 1.0×10 23 atom / cm 3 the following.

[0020] Effects of the Invention

[0021] According to the present invention, it is possible to provide an organic EL display device that can shorten the production cycle and has high reliability. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] [ Figure 1 ]Cross-sectional view of a TFT substrate with a planarization layer and a pixel division layer

[0023] [ Figure 2 ] A process diagram showing an example of a manufacturing process of an organic EL display device of the present invention

[0024] [ Figure 3 ] A schematic diagram illustrating the steps of manufacturing an organic EL display device manufactured in the embodiment DETAILED DESCRIPTION

[0025] The present invention is an organic EL display device, which is an organic EL display device having at least a substrate, a first electrode, a second electrode, a light-emitting layer, a planarization layer and a pixel division layer, wherein the planarization layer or the pixel division layer has a cured product obtained by exposing, developing and curing the following resin composition A or resin composition B:

[0026] [Resin composition A] A resin composition comprising (A-1) a resin having an alkali-soluble group protected by a protecting group that can be removed by an acid (hereinafter, sometimes referred to as "resin (A-1)") and (B) a photoacid generator,

[0027] [Resin composition B] A resin composition comprising a resin having an alkali-soluble group, (A-2) a compound having an alkali-soluble group protected by a protecting group capable of being removed by an acid (hereinafter, sometimes referred to as "compound (A-2)"), and (B) a photoacid generator,

[0028] The total content of metal elements and halogen elements in the cured product measured by time-of-flight secondary ion mass spectrometry was 1.0×10 16 atom / cm 3 Above 1.0×10 23 atom / cm 3 the following.

[0029] <Basic Structure of Organic EL Display Device>

[0030] The organic EL display device of the present invention has at least a substrate, a first electrode, a second electrode, a light-emitting layer, a planarization layer, and a pixel segmentation layer. The organic EL display device of the present invention is preferably an active matrix type organic EL display device having a plurality of pixels formed in a matrix. In an active matrix type organic EL display device, a thin film transistor for wiring and driving is arranged on a substrate such as glass, and the thin film transistor is electrically connected to the first electrode, and a light-emitting layer and a second electrode are stacked on the first electrode. The stacked structure of the first electrode / light-emitting layer / second electrode is arranged in a matrix on the substrate to form a screen.

[0031] Figure 1A cross-sectional view of an example of a TFT substrate having a planarization layer and a pixel division layer is shown in FIG. On a substrate 6, bottom-gate or top-gate TFTs 1 are arranged in rows and columns, and a TFT insulating layer 3 is formed in a state of covering the TFTs 1. In addition, a wiring 2 connected to the TFTs 1 is provided under the TFT insulating layer 3. In addition, on the TFT insulating layer 3, a planarization layer 4 having a contact hole 7 opened in a portion of the wiring 2 is provided. Moreover, an ITO 5 (transparent electrode) is formed on the planarization layer 4 in a state of being electrically connected to the wiring 2 via the contact hole 7. Here, the ITO 5 becomes the first electrode of the organic EL display device. Moreover, a pixel division layer 8 is formed in a manner covering the periphery of the ITO 5.

[0032] The organic EL display device of the present invention may be a top emission type in which light is emitted from the side opposite to the substrate 6 , or may be a bottom emission type in which light is extracted from the substrate 6 side.

[0033] For an organic EL display device, a light-emitting layer corresponding to red, green, and blue is provided on the first electrode of such a TFT substrate, and a second electrode is provided, or a white light-emitting layer, a second electrode, and a color filter are provided on the first electrode, so that color display can be performed. In a display capable of color display, the peak wavelength of light in the red region displayed is usually in the range of 560 to 700 nm, the peak wavelength of light in the green region is in the range of 500 to 560 nm, and the peak wavelength of light in the blue region is in the range of 420 to 500 nm.

[0034] <Method for manufacturing organic EL display device>

[0035] An outline of a method for manufacturing an organic EL display device according to an embodiment of the present invention will be described with examples. Figure 2 This is a diagram showing an example (it should be noted that the TFT substrate uses Figure 1). For the organic EL display device of the present invention, TFT 10 is formed on substrate 9, and then a planarization layer 11 is formed. A first electrode 12 is formed on the planarization layer 11. Then, a photosensitive resin composition is applied and pre-baked to form a pre-baked film 13. Then, active chemical rays 15 are irradiated through a mask 14 having a desired pattern. Then, development is performed and pattern processing is performed to cure it, thereby forming a pixel segmentation layer 16 and a light-emitting layer 17, and a second electrode 18 is further formed on the light-emitting layer, thereby obtaining the organic EL display device of the present invention. The planarization layer 11 and the pixel segmentation layer 16 can be formed, for example, by applying a photosensitive resin composition described later, pattern processing using photolithography, and curing it. After the second electrode is formed, it is preferably sealed. It is generally believed that organic EL display devices have weak resistance to oxygen and moisture. In order to obtain a display device with high reliability, it is preferably sealed in an atmosphere with as little oxygen and moisture as possible.

[0036] <Substrate>

[0037] As the substrate, a glass substrate such as soda-lime glass or alkali-free glass, or a flexible substrate such as polyethylene terephthalate film or polyimide film can be preferably used. The thickness of the glass substrate is preferably 0.5 mm or more. From the perspective of less ions eluted from the glass, the material of the glass substrate is preferably alkali-free glass, soda-lime glass obtained by barrier coating based on silicon oxide (SiO2), etc.

[0038] <First Electrode>

[0039] In order to efficiently inject holes into the organic layer and extract light, the first electrode is preferably transparent or translucent. As the material constituting the first electrode, for example, conductive metal oxides such as zinc oxide, tin oxide, indium oxide, indium tin oxide (ITO), indium zinc oxide (IZO), gold, silver, chromium and other metals, inorganic conductive materials such as copper iodide, copper sulfide, polythiophene, polypyrrole, polyaniline and other conductive polymers, carbon nanotubes, graphene, etc. can be cited. Two or more of them can be used, and the stacked structure formed by different materials can also be provided. In addition, its form is not particularly limited, for example, it is possible to have the fine structure such as metal mesh, silver nanowires.

[0040] From the viewpoint of power consumption of the organic EL display device, the first electrode is preferably low-resistance. For example, in the case of an ITO substrate, as long as the resistance value is 300Ω / □ (the unit can also be expressed as Ω / sq., or ohm per square) or less, it functions as an element electrode, but substrates of about 10Ω / □ are now available, so it is more preferable to use a substrate with a low resistance of less than 20Ω / □. The thickness of the first electrode can be arbitrarily selected according to the resistance value, and is usually about 45 to 300nm.

[0041] <Second Electrode>

[0042] The second electrode is preferably capable of efficiently injecting electrons into the light-emitting layer. As the material constituting the second electrode, for example, metals such as platinum, gold, silver, copper, iron, tin, aluminum, indium, and alloys of these metals with low work function metals such as lithium, sodium, potassium, calcium, and magnesium can be cited. Two or more of them can be used, and a stacked structure formed by different materials can also be provided. Among them, from the aspects of resistance value, ease of film making, stability of the film, luminous efficiency, etc., aluminum, silver, and magnesium are preferably used as the main components. It is more preferred to contain magnesium and silver, so that the electron injection into the light-emitting layer becomes easy, and the driving voltage can be further reduced.

[0043] Examples of the method for forming the first electrode and the second electrode include resistance heating, electron beam, sputtering, ion plating, coating, and the like.

[0044] Among the first electrode and the second electrode, the electrode used as the cathode preferably has a protective layer on the electrode. As the material constituting the protective layer, for example, inorganic substances such as silicon dioxide, titanium dioxide, and silicon nitride, organic polymer compounds such as polyvinyl alcohol, polyvinyl chloride, and hydrocarbon polymer compounds can be cited. In the case of a top emission structure that extracts light from the cathode side, the material constituting the protective layer is preferably a material that is light-transmissive in the visible light region.

[0045] <Layers that make up a pixel>

[0046] The light-emitting layer is arranged at the portion where the first electrode and the second electrode arranged opposite to each other cross and overlap, and when a pixel segmentation layer is formed on the first electrode, it can be further arranged within the range limited by the pixel segmentation layer. That is, the light-emitting layer is separated by the pixel segmentation layer. The shape of the light-emitting layer, that is, the shape seen from the viewer side, is not particularly limited, for example, it can be rectangular or circular, and can be formed in any shape according to the shape of the pixel segmentation layer. In an active matrix display, it is sometimes configured in a manner that the portion to be formed of the switching mechanism occupies a portion of the substrate, and the shape of the light-emitting layer can also be a shape in which a portion of a rectangle or a circle is missing.

[0047] In addition, a layer other than the light-emitting layer may be provided between the first electrode and the second electrode, and as such a structure, for example, an electron transport layer, a hole transport layer, an electron injection layer, a hole injection layer, and the like used in an organic EL element may be cited. Specifically, for example, 1) light-emitting layer / electron transport layer, 2) hole transport layer / light-emitting layer, 3) hole transport layer / light-emitting layer / electron transport layer, 4) hole injection layer / hole transport layer / light-emitting layer / electron transport layer, 5) hole transport layer / light-emitting layer / electron transport layer / electron injection layer, 6) hole injection layer / hole transport layer / light-emitting layer / electron transport layer / electron injection layer and the like stacked structures may be cited.

[0048] In the present invention, it is also possible to further stack a plurality of the above-mentioned stacked structures via an intermediate layer to obtain a series type. The intermediate layer is also generally referred to as an intermediate electrode, an intermediate conductive layer, a charge generation layer, an electron extraction layer, a connecting layer, and an intermediate insulating layer. As a series type structure, for example, 7) hole transport layer / luminescent layer / electron transport layer / charge generation layer / hole transport layer / luminescent layer / electron transport layer, 8) hole injection layer / hole transport layer / luminescent layer / electron transport layer / electron injection layer / charge generation layer / hole injection layer / hole transport layer / luminescent layer / electron transport layer / electron injection layer, etc. can be cited as a stacked structure including a charge generation layer as an intermediate layer. As a material constituting the intermediate layer, pyridine derivatives and phenanthroline derivatives are preferred.

[0049] In addition, for each of the above-mentioned layers, different materials may be used, for example, so that the electron transport layer is divided into two layers, thereby forming a layer composed of a plurality of materials.

[0050] <Hole Injection Layer>

[0051] The hole injection layer is inserted between the anode and the hole transport layer to facilitate the transfer of holes from the anode to the hole transport layer. If there is a hole injection layer between the hole transport layer and the anode, it can be driven at a lower voltage, which can improve the durability life. In addition, the carrier balance of the organic EL display device is improved, so the luminous efficiency can be improved.

[0052] As materials constituting the hole injection layer, for example, 4,4'-bis(N-(3-methylphenyl)-N-phenylamino)biphenyl (TPD), 4,4'-bis(N-(1-naphthyl)-N-phenylamino)biphenyl (NPD), bis(N-arylcarbazole), bis(N-alkylcarbazole) and other biscarbazole derivatives can be cited. The hole injection layer can use two or more of these materials, and can also have a stacked structure formed of different materials.

[0053] The hole injection layer is preferably doped with an acceptor compound. The so-called acceptor compound is a material that forms a charge transfer complex with the material constituting the hole injection layer. By using such an acceptor compound, the conductivity of the hole injection layer is improved, the driving voltage of the organic EL display device can be further reduced, and the luminous efficiency and durability life can be further improved.

[0054] As acceptor compounds, for example, metal oxides, organic compounds having a nitro group, a cyano group, a halogen or a trifluoromethyl group in the molecule, quinone compounds, acid anhydride compounds, fullerene, etc. Among them, metal oxides and organic compounds containing a cyano group are preferred from the perspective of easy handling and easy vapor deposition.

[0055] <Hole Transport Layer>

[0056] The hole transport layer is a layer that transports holes injected from the anode to the light-emitting layer. The hole transport layer may be a single layer or may be composed of a plurality of layers stacked together. The hole transport layer preferably has an ionization potential of 5.1 to 6.0 eV (AC-2 (Riken Keiki) measurement value of the vapor-deposited film), a high triplet energy level, high hole transport properties, and thin film stability. The hole transport layer can be used as a hole transport material for an organic EL display device using a triplet light-emitting material. As materials constituting the hole transport layer, for example, the materials exemplified as materials constituting the hole injection layer can be cited.

[0057] <Luminous Layer>

[0058] The light-emitting layer is a layer that uses the recombination energy generated by the collision of holes and electrons to excite the light-emitting material to emit light. The light-emitting layer can be a single layer or a plurality of layers stacked. The light-emitting layer contains a light-emitting material (host material, dopant material). When the light-emitting layer is composed of a plurality of layers, each layer can be composed of only one of the host material or the dopant material, or a combination of more than one host material and more than one dopant material. When the light-emitting layer contains a host material and a dopant material, only one of the host material and the dopant material can emit light, or both the host material and the dopant material can emit light. From the perspective of efficiently utilizing electrical energy and obtaining light with high color purity, the light-emitting layer is preferably composed of a combination of a host material and a dopant material. Regarding the content of the dopant material in the light-emitting layer, from the perspective of suppressing the concentration quenching phenomenon, it is preferably 30 parts by weight or less, and more preferably 20 parts by weight or less, relative to 100 parts by weight of the host material. The light-emitting layer can be formed by a method of co-evaporating the host material and the dopant material, a method of pre-mixing the host material and the dopant material and then evaporating, and the like.

[0059] As dopant materials, for example, there can be mentioned fused ring derivatives such as anthracene and pyrene, metal coordination compounds such as tris(8-hydroxyquinoline)aluminum, distyryl derivatives such as distyryl anthracene derivatives and distyryl benzene derivatives, tetraphenylbutadiene derivatives, dibenzofuran derivatives, carbazole derivatives, indolecarbazole derivatives, polyphenylene vinylene derivatives, and the like.

[0060] As a dopant material used when triplet luminescence (phosphorescent luminescence) is performed in the light-emitting layer, it is preferably a metal coordination compound containing at least one metal selected from the group consisting of iridium (Ir), ruthenium (Ru), palladium (Pd), platinum (Pt), osmium (Os) and rhenium (Re). The ligand constituting the metal coordination compound can be appropriately selected according to the required luminescent color, the performance of the organic EL display device, and the relationship with the host compound, preferably having a nitrogen-containing aromatic heterocycle such as a phenylpyridine skeleton, a phenylquinoline skeleton, and a carbene skeleton, specifically, tris (2-phenylpyridyl) iridium complex, bis (2-phenylpyridyl) (acetylacetone) iridium complex, tetraethylporphyrin platinum complex, etc. It is also possible to use two or more of them to constitute a metal coordination compound.

[0061] Examples of the host material include naphthalene, anthracene, phenanthrene, pyrene, Compounds having a condensed aromatic ring such as tetracene, tri-o-phenylene, perylene, fluoranthene, fluorene, indene, etc. Two or more of these may be used to constitute the light-emitting material.

[0062] As the host material used when the light-emitting layer performs triplet luminescence (phosphorescence), metal chelated oxadiazole compounds, dibenzofuran derivatives, dibenzothiophene derivatives, carbazole derivatives, indolecarbazole derivatives, triazine derivatives, tri-o-phenylene derivatives, etc. can be preferably used. Among them, compounds having anthracene skeletons and pyrene skeletons are more preferred because they are easy to obtain high-efficiency luminescence.

[0063] <Electron Transport Layer>

[0064] The electron transport layer is a layer that transfers electrons injected from the cathode to the light-emitting layer. For the electron transport layer, it is expected that the electron injection efficiency is high and the injected electrons are efficiently transported. Therefore, the electron transport layer is preferably a substance with large electron affinity and electron mobility, excellent stability, and impurities that are not easy to produce traps during manufacture and use. Especially when the film thickness of the electron transport layer is thick, low molecular weight compounds will crystallize, etc., and the film quality is easy to deteriorate. Therefore, compounds with a molecular weight of more than 400 are preferred. It should be noted that, considering the transmission balance of holes and electrons, as long as the electron transport layer mainly plays a role in efficiently preventing holes from the anode from recombining and flowing to the cathode side, even if it is composed of a material with not so high electron transport ability, the effect of improving the luminous efficiency is equivalent to that of a material with high electron transport ability. Therefore, in the electron transport layer in the present invention, a hole blocking layer that can efficiently prevent holes from moving is also included as a synonymous layer. The electron transport layer can be a single layer or a plurality of layers can be stacked and constituted.

[0065] As the electron transport material constituting the electron transport layer, for example, condensed polycyclic aromatic derivatives such as naphthalene and anthracene can be cited. Two or more of them can also be used. Among them, from the perspective of further reducing the driving voltage and obtaining efficient luminescence, it is preferably a compound having a heteroaryl ring structure containing electron accepting nitrogen.

[0066] Here, the so-called electron accepting nitrogen refers to a nitrogen atom that forms a heavy bond with an adjacent atom. Since the nitrogen atom has a high electronegativity, the heavy bond has the property of electron accepting. Therefore, the aromatic heterocycle containing electron accepting nitrogen has a high electron affinity. The electron transport material with electron accepting nitrogen easily receives electrons from the cathode with high electron affinity, so the driving voltage can be further reduced. In addition, the electron transport material with electron accepting nitrogen supplies more electrons to the light-emitting layer, and the recombination probability becomes higher, so the luminous efficiency is improved.

[0067] As the heteroaryl ring containing electron accepting nitrogen, for example, triazine ring, pyridine ring, etc. can be cited. As compounds having these heteroaryl ring structures, from the viewpoint of electron transport ability, triazole derivatives such as N-naphthyl-2,5-diphenyl-1,3,4-triazole, bipyridine derivatives such as 2,5-bis(6'-(2',2"-bipyridyl))-1,1-dimethyl-3,4-diphenylthiole, terpyridine derivatives such as 1,3-bis(4'-(2,2':6'2"-terpyridyl))benzene, or two or more thereof are preferably used.

[0068] The electron transport layer may contain a donor compound. Here, the donor compound is a compound that improves the electron injection barrier to facilitate the injection of electrons from the cathode or the electron injection layer into the electron transport layer, thereby further improving the conductivity of the electron transport layer.

[0069] Examples of the donor compound include alkali metals, inorganic salts of alkali metals, complexes of alkali metals and organic substances, alkaline earth metals, inorganic salts of alkaline earth metals, and complexes of alkaline earth metals and organic substances.

[0070] Regarding donor compounds, inorganic salts or complexes with organic substances are preferred over metal elements because of their ease of vapor deposition in a vacuum and excellent operability. Complexes with organic substances are more preferred because of their ease of operation in the atmosphere and ease of adjusting the added concentration.

[0071] The ionization potential of the electron transport layer is preferably 5.6 eV or more, and more preferably 6.6 eV or more. On the other hand, it is preferably 8.0 eV or less, and more preferably 7.0 eV or less.

[0072] As a method for forming the above-mentioned layers constituting the organic EL display device, for example, resistance heating evaporation method, electron beam evaporation method, sputtering method, molecular lamination method, coating method, etc. can be cited. Among them, resistance heating evaporation method and electron beam evaporation method are preferred from the viewpoint of the characteristics of the organic EL display device.

[0073] The total thickness of the organic layer including the hole injection layer, the hole transport layer, the light-emitting layer, and the electron transport layer can be appropriately selected according to the resistance value of the light-emitting substance, and is preferably 1 to 1000 nm. The thickness of the hole injection layer, the hole transport layer, the light-emitting layer, and the electron transport layer is preferably 1 nm or more, and more preferably 5 nm or more. On the other hand, the thickness of the hole injection layer, the hole transport layer, the light-emitting layer, and the electron transport layer is preferably 200 nm or less, and more preferably 100 nm or less.

[0074] <Planarization layer and pixel segmentation layer>

[0075] In the present invention, the planarization layer or the pixel division layer is characterized in that it has a cured product obtained by exposing, developing, and curing the resin composition described below, and preferably consists of the cured product, wherein the total content of the metal element and the halogen element in the cured product measured by time-of-flight secondary ion mass spectrometry is 1.0×10 16 atom / cm 3 Above 1.0×10 23 atom / cm 3 As follows. Of course, both the planarization layer and the pixel segmentation layer may have the above-mentioned features. By making the cured product contain trace amounts of metal elements and halogen elements, the conductivity of the pattern opening can be improved by utilizing the trace amounts of metal elements and halogen elements attached to the substrate when the planarization layer or the pixel segmentation layer is formed using the aforementioned resin composition. Therefore, the driving voltage of the organic EL display device can be reduced and the reliability can be improved. In addition, these elements can form salts with the resin (A-1) having an alkali-soluble group protected by a protecting group that can be detached by an acid, or (A-2) having an alkali-soluble group protected by a protecting group that can be detached by an acid, through the element capture effect. This can inhibit electrode corrosion caused by alkali migration of excess metal elements and halogen elements, resulting in reduced luminous brightness and pixel shrinkage, and improve the reliability of the organic EL display device. If the sum of the contents of metal elements and halogen elements in the cured product is less than 1.0×10 16 atom / cm 3 , the conductivity of the ITO electrode forming the pattern opening is low, and when the organic EL display device is driven for a long time, high voltage is likely to occur, thereby reducing reliability. On the other hand, if the sum of the contents of metal elements and halogen elements is greater than 1.0×10 23 atom / cm 3, the excess metal elements and halogen elements that cannot be captured by the element capture effect are prone to electrode corrosion in the pattern opening. Therefore, when the organic EL display device is driven for a long time, the reliability is reduced due to the reduction of luminous brightness and pixel shrinkage.

[0076] It should be noted that the meaning of "cured product obtained by exposure, development, and curing" is that the resin composition used in the present invention becomes a cured product through the steps of exposure, development, and curing, and does not necessarily mean that the exposed portion becomes a cured product. That is, it includes a cured product obtained by curing the unexposed portion that remains as a result of development.

[0077] In the present invention, as a method for adjusting the metal element and the halogen element to the above-mentioned range, for example, there is a method of using a resin composition described later.

[0078] It should be noted that, herein, the so-called metallic element refers to an element showing the properties of a metal in a simple state, including the case of an ion. In addition, when the metallic element is an alkali metal element or an alkaline earth metal element, especially when it is sodium or potassium, in the resin composition described later, it is easy to be captured by forming and interacting with a salt of resin (A-1) or compound (A-2). In addition, the so-called halogen element refers to an element belonging to Group 17 in the periodic table, including the case of an ion. In addition, when the halogen element is chlorine, in the resin composition described later, it is easy to form a salt with resin (A-1) or compound (A-2) and be captured, so the reliability of the organic EL display device can be further improved.

[0079] In the present invention, in the cured product obtained by subjecting the resin composition described below to exposure, development, and curing, the total content of the metal element and the halogen element measured by time-of-flight secondary ion mass spectrometry is 1.0×10 16 atom / cm 3 Above 1.0×10 23 atom / cm 3 the following.

[0080] The total content of metal elements and halogen elements in the cured product is 1.0×10 16 atom / cm 3 As described above, the driving voltage of the organic EL display device can be further reduced, and the reliability can be further improved. 23 atom / cm 3 The lower limit of the total content of the metal element and the halogen element in the cured product is preferably set to 1.0×10 17ato m / cm 3 The upper limit is preferably set to 1.0×10 22 atom / cm 3 the following.

[0081] In addition, the total content of sodium and potassium in the metal elements is preferably 1.0×10 17 atom / cm 3 Above 1.0×10 22 atom / cm 3 The total content of fluorine and chlorine in the halogen is preferably 1.0×10 17 atom / cm 3 Above 1.0×10 22 atom / cm 3 By falling within this range, the driving voltage of the organic EL display device can be further reduced, and the reliability can be further improved.

[0082] <Quantitative Method for Metal Elements and Halogen Elements>

[0083] The metal elements and halogen elements in the cured product of the resin composition can be quantified by the following method. First, a specific amount of the target element is injected into the cured film using IMX-3500RS (manufactured by ULVAC), and the relative sensitivity factor (RSF) is calculated using the following formula. In order to make the sensitivity (atom / cm 3 ) is good, and the ion implantation amount is preferably 1.0×10 13 atom / cm 2 ~5.0×10 15 atom / cm 2 Regarding the measurement conditions, in the case of cation detection, the etching ion species is O2 + , the etching ion acceleration energy is 2keV, and the primary ion species is Bi + , the ion energy is 25keV, and the charge compensation is performed using Metal-coat and e-gun. In the case of negative ion detection, the etching ion species is C s + , the etching ion acceleration energy is 2keV, and the primary ion species is Bi + The primary ion energy was 25 keV, and charge compensation was performed using an e-gun. TOF-SIMS analysis used TOF.SIMS5 manufactured by ION-TOF.

[0084] [Mathematical formula 1]

[0085]

[0086] Φ0: Ion implantation amount (atom / cm 2 )

[0087] Δd0: Depth per measurement cycle (cm)

[0088] I i :Impurity ion strength (counts)

[0089] I BG : Background intensity (counts)

[0090] I ref :Ionic strength of cured film (counts)

[0091] Based on the obtained relative sensitivity coefficient, the concentrations of the metal element and the halogen element (target element) in the cured film can be quantified by TOF-SI MS analysis using the following formula.

[0092] Target element concentration = RSF (atom / cm 3 )× target element ionic strength (counts) / cured film ionic strength (counts).

[0093] In addition, the site|part used for quantitative measurement was calculated at the position of 0.5 micrometer from the surface layer of a cured film.

[0094] <Aperture Ratio of Pixel Division Layer>

[0095] In the present invention, the aperture ratio of the pixel segmentation layer is preferably 20% or less. Here, the so-called aperture ratio of the pixel segmentation layer refers to the ratio of the area of ​​the opening of the pixel segmentation layer to the overall area of ​​the organic EL display device. If the pixels are made more refined, the aperture ratio of the pixel segmentation layer becomes lower and the effect of pixel shrinkage becomes greater. The organic EL display device of the present invention can suppress the reduction of luminous brightness and pixel shrinkage, thereby improving the reliability of the organic EL display device. Therefore, when the effect of pixel shrinkage is large and the aperture ratio of the pixel segmentation layer is 20% or less, a particularly significant effect is exerted.

[0096] It should be noted that, here, the so-called "area of ​​the entire organic EL display device" refers to the area of ​​the entire display of a smartphone, tablet computer, etc., and the "opening of the pixel division layer" refers to the area of ​​the pixel in the display. As for the specific measurement method, the area can be obtained by direct observation using a microscope or the like.

[0097] <Resin composition>

[0098] In the present invention, the planarization layer or the pixel division layer is formed of a cured product obtained by subjecting the resin composition A or the resin composition B described below to exposure, development, and curing.

[0099] [Resin composition A] A resin composition comprising (A-1) a resin having an alkali-soluble group protected by a protecting group that can be removed by acid and (B) a photoacid generator

[0100] [Resin composition B] A resin composition comprising a resin having an alkali-soluble group, (A-2) a compound having an alkali-soluble group protected by a protecting group capable of being removed by an acid, and (B) a photoacid generator

[0101] The above-mentioned resin composition A and resin composition B may further contain other components.

[0102] <Resin having an alkali-soluble group>

[0103] In the present invention, the so-called alkali solubility refers to the property of having solubility in a tetramethylammonium hydroxide aqueous solution with a concentration of 25 mass %, and by having such a property, development based on a general developer can be achieved. As a functional group (alkali soluble group) for making the resin alkali soluble, it is preferred to use a carboxyl group or a hydroxyl group, which is easy to improve the solubility in an alkaline developer, and in terms of resolution, it is also easy to achieve a higher resolution.

[0104] It should be noted that, in order to avoid confusion, in the present invention, when simply referred to as "resin having an alkali-soluble group", it means a resin that does not have an alkali-soluble group protected by a protecting group that can be removed by acid, and a resin that has an alkali-soluble group protected by a protecting group that can be removed by acid in part is also referred to as "resin having an alkali-soluble group protected by a protecting group that can be removed by acid". In addition, a resin having an alkali-soluble group protected by a protecting group that can be removed by acid does not necessarily have alkali solubility in a state where the alkali-soluble group is protected by a protecting group. However, it has alkali solubility in a state where the protecting group is removed.

[0105] As the resin having an alkali-soluble group, it is preferred that the resin is selected from the group consisting of polyimide, polybenzoxazole, polyimide precursor, polybenzoxazole precursor and copolymers thereof, and is a resin having an alkali-soluble group in its structure, and may contain two or more of them. Polyimide and polybenzoxazole are resins having a cyclic structure of an imide ring or an oxazole ring in the main chain. The number of repetitions of the repeating unit is preferably 10 to 100,000.

[0106] Polyimide can be obtained by reacting tetracarboxylic acid, corresponding tetracarboxylic dianhydride, tetracarboxylic diester dichloride, etc. with diamine, corresponding diisocyanate compound, trimethyl silylated diamine, and has tetracarboxylic acid residue and diamine residue. For example, it can be obtained by the following method: by heat treatment, chemical treatment, dehydration ring closure of polyamic acid as one of polyimide precursors obtained by reacting tetracarboxylic dianhydride with diamine. During the heat treatment, a solvent such as m-xylene that azeotropes with water can also be added. In addition, a weakly acidic carboxylic acid compound can also be added and heat treated at a low temperature below 100°C. As the ring closure catalyst used in the chemical treatment, dehydration condensation agents such as carboxylic anhydride, dicyclohexylcarbodiimide, bases such as triethylamine, etc. can be cited. About the polyimide precursor, it is described later.

[0107] Polybenzoxazole can be obtained by reacting a bisaminophenol compound with a dicarboxylic acid, a corresponding diacyl chloride, a dicarboxylic acid active ester, etc., and has a dicarboxylic acid residue and a bisaminophenol residue. For example, it can be obtained by the following method: by heat treatment, chemical treatment, dehydration ring closure is carried out on the polyhydroxyamide as one of the polybenzoxazole precursors obtained by reacting a bisaminophenol compound with a dicarboxylic acid. During the heat treatment, a solvent such as m-xylene that azeotropes with water can also be added. In addition, an acidic compound can also be added and heat treated at a low temperature below 200°C. As the ring-closure catalyst used in the chemical treatment, phosphoric anhydride, alkali, carbodiimide compounds, etc. can be cited. About the polybenzoxazole precursor, it will be described later.

[0108] In the present invention, from the viewpoint of solubility in alkaline aqueous solution, the polyimide preferably has an OR 7 、SO3R 7 ,CONR 7 R 8 、COO R 7 、SO2NR 7 R 8 In addition, polybenzoxazole preferably has an OR on the dicarboxylic acid residue or bisaminophenol residue. 7 、SO3R 7 ,CONR 7 R 8 、COOR 7 、SO2NR 7 R 8 It is more preferably an acidic group or a group derived from an acidic group, and more preferably has a hydroxyl group. 7 and R 8 represents a hydrogen atom or a monovalent organic group having 1 to 20 carbon atoms. 7 or R 8The group derived from the acidic group refers to the group R 7 or R 8 In the case of a monovalent organic group having 1 to 20 carbon atoms.

[0109] In the present invention, preferred structures of the tetracarboxylic acid residue of the polyimide and the dicarboxylic acid residue of the polybenzoxazole (hereinafter, they are collectively referred to as "acid residue") include the following structures or structures obtained by replacing 1 to 4 of their hydrogen atoms with alkyl groups having 1 to 20 carbon atoms, fluoroalkyl groups, alkoxy groups, ester groups, nitro groups, cyano groups, fluorine atoms, or chlorine atoms. Two or more of these may be used.

[0110] [Chemical formula 1]

[0111]

[0112] [Chemical formula 2]

[0113]

[0114] Wherein, J represents a direct bond, -COO-, -CONH-, -CH2-, -C2H4-, -O-, -C3H6-, -SO2-, -S-, -Si(CH3)2-, -O-Si(CH3)2-O-, -C6H4-, -C6H4-O-C6H4-, -C6H4-C3H6-C6H4- or -C6H4-C3F6-C6H4-.

[0115] In the present invention, preferred structures of the diamine residue of the polyimide and the bisaminophenol residue of the polybenzoxazole (hereinafter collectively referred to as "amine residue") include the following structures or structures obtained by replacing 1 to 4 of their hydrogen atoms with alkyl groups having 1 to 20 carbon atoms, fluoroalkyl groups, alkoxy groups, ester groups, nitro groups, cyano groups, fluorine atoms, or chlorine atoms. Two or more of these may be used.

[0116] [Chemical formula 3]

[0117]

[0118] [Chemical formula 4]

[0119]

[0120] Here, J represents a direct bond, -COO-, -CONH-, -CH2-, -C2H4-, -O-, -C3H6-, -SO2-, -S-, -Si(CH3)2-, -O-Si(CH3)2-O-, -C6H4-, -C6H4-O-C6H4-, -C6H4-C3H6-C6H4-, or -C6H4-C3F6-C6H4-. R 7 It represents a hydrogen atom or a monovalent organic group having 1 to 20 carbon atoms.

[0121] The polyimide precursor and the polybenzoxazole precursor have an amide bond on the main chain, and are dehydrated and ring-closed by heat treatment and chemical treatment to form polyimide and polybenzoxazole. The number of repetitions of the repeating unit is preferably 10 to 100,000. As polyimide precursors, polyamic acid, polyamic acid esters, polyamic acid amides, polyisoimides, etc. can be cited, preferably polyamic acid and polyamic acid esters. As polybenzoxazole precursors, polyhydroxyamides, polyaminoamides, polyamides, polyamide-imides, etc. can be cited, preferably polyhydroxyamides. From the viewpoint of solubility in alkaline aqueous solutions, polyimide precursors and polybenzoxazole precursors preferably have OR on acid residues or amine residues. 7 、SO3R 7 ,CONR 7 R 8 、COO R 7 、SO2NR 7 R 8 It is more preferably an acidic group or a group derived from an acidic group, and more preferably has a hydroxyl group. 7 and R 8 It represents a hydrogen atom or a monovalent organic group having 1 to 20 carbon atoms. The acidic group and the group derived from the acidic group have the same meaning as used in the above description of the polyimide and polybenzoxazole (the same also applies hereinafter).

[0122] Examples of dicarboxylic acids that constitute the acid residues of the polyimide precursor and the polybenzoxazole precursor include terephthalic acid, isophthalic acid, diphenyl ether dicarboxylic acid, bis(carboxyphenyl)hexafluoropropane, biphenyl dicarboxylic acid, benzophenone dicarboxylic acid, and triphenyl dicarboxylic acid. Examples of tricarboxylic acids include trimellitic acid, trimesic acid, diphenyl ether tricarboxylic acid, and biphenyl trimaric acid. Examples of tetracarboxylic acids include pyromellitic acid, 3,3',4,4'-biphenyltetracarboxylic acid, 2,3,3',4'-biphenyltetracarboxylic acid, 2,2',3,3'-biphenyltetracarboxylic acid, 3,3',4,4'-benzophenonetetracarboxylic acid, 2,2',3,3'-benzophenonetetracarboxylic acid, 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane, 2,2-bis(2,3-dicarboxyphenyl)hexafluoropropane, 1,1-bis(3,4-dicarboxyphenyl)ethane, 1,1-bis(2,3-dicarboxyphenyl)ethane, bis(3,4-dicarboxyphenyl)methane, bis(2,3-dicarboxyphenyl)ethane, 1,1-bis(2,3-dicarboxyphenyl)ethane, 1,1-bis(3,4-dicarboxyphenyl)ethane, 1,1- ... Aromatic tetracarboxylic acids such as 1,2,5,6-naphthalenetetracarboxylic acid, 2,3,6,7-naphthalenetetracarboxylic acid, 2,3,5,6-pyridinetetracarboxylic acid, and 3,4,9,10-perylenetetracarboxylic acid, and aliphatic tetracarboxylic acids such as butanetetracarboxylic acid, cyclobutanetetracarboxylic acid, 1,2,3,4-cyclopentanetetracarboxylic acid, cyclohexanetetracarboxylic acid, bicyclo[2.2.1.]heptanetetracarboxylic acid, bicyclo[3.3.1.]tetracarboxylic acid, bicyclo[3.1.1.]hept-2-enetetracarboxylic acid, bicyclo[2.2.2.]octanetetracarboxylic acid and adamantanetetracarboxylic acid may be used. Two or more of these may be used. In addition, it is more preferred that 1 to 4 of the hydrogen atoms of the dicarboxylic acids, tricarboxylic acids, or tetracarboxylic acids exemplified above are replaced by OR 7 、SO3R 7 ,CONR 7 R 8 、COOR 7 、SO2NR 7 R 8 or a group derived from an acidic group (preferably a hydroxyl group, a sulfonic acid group, a sulfonamide group, a sulfonic ester group, etc.). 7 and R 8 It represents a hydrogen atom or a monovalent organic group having 1 to 20 carbon atoms.

[0123] These acids may be used directly or in the form of anhydrides or active esters.

[0124] In addition, by using a tetracarboxylic acid containing a silicon atom such as dimethylsilanediphthalic acid and 1,3-bis(phthalic acid)tetramethyldisiloxane, it is possible to improve adhesion to a substrate and resistance to oxygen plasma and UV ozone treatment used for cleaning, etc. These tetracarboxylic acids containing a silicon atom are preferably used in an amount of 1 to 30 mol% of the total acid components.

[0125] Examples of the diamine component constituting the amine residue of the polyimide precursor and the polybenzoxazole precursor include bis(3-amino-4-hydroxyphenyl)hexafluoropropane, bis(3-amino-4-hydroxyphenyl)sulfone, bis(3-amino-4-hydroxyphenyl)propane, bis(3-amino-4-hydroxyphenyl)methylene, bis(3-amino-4-hydroxyphenyl)ether, bis(3-amino-4-hydroxy)biphenyl, bis(3-amino-4-hydroxyphenyl)fluorene and other hydroxyl-containing diamines, 3,5-diamino Benzoic acid, diamines containing carboxyl groups such as 3-carboxy-4,4'-diaminodiphenyl ether, diamines containing sulfonic acid such as 3-sulfonic acid-4,4'-diaminodiphenyl ether, dithiophenylene diamine, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether , 1,4-bis(4-aminophenoxy)benzene, petroleum spirit, m-phenylenediamine, p-phenylenediamine, 1,5-naphthalenediamine, 2,6-naphthalenediamine, bis(4-aminophenoxyphenyl)sulfone, bis(3-aminophenoxyphenyl)sulfone, bis(4-aminophenoxy)biphenyl, bis{4-(4-aminophenoxy)phenyl}ether, 1,4-bis(4-aminophenoxy)benzene, 2,2'-dimethyl-4,4'-diaminobiphenyl, 2,2'-diethyl-4,4'-diaminobiphenyl, 3,3' -dimethyl-4,4'-diaminobiphenyl, 3,3'-diethyl-4,4'-diaminobiphenyl, 2,2',3,3'-tetramethyl-4,4'-diaminobiphenyl, 3,3',4,4'-tetramethyl-4,4'-diaminobiphenyl, 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, or compounds obtained by replacing part of the hydrogen atoms of their aromatic rings with alkyl groups or halogen atoms, aliphatic diamines such as cyclohexyldiamine and methylenebiscyclohexylamine, etc. In addition, these diamines may be substituted by alkyl groups having 1 to 10 carbon atoms such as methyl and ethyl groups, fluoroalkyl groups having 1 to 10 carbon atoms such as trifluoromethyl groups, F, Cl, Br, I and the like. Two or more of them may also be used. In applications requiring heat resistance, it is preferred to use aromatic diamines in an amount of 50 mol% or more of the total diamine. In addition, the diamines exemplified above preferably have OR 7 、SO3R 7 ,CONR 7 R 8、COOR 7 、SO2NR 7 R 8 It should be noted that R 7 and R 8 It represents a hydrogen atom or a monovalent organic group having 1 to 20 carbon atoms.

[0126] These diamines may be used directly or in the form of corresponding diisocyanate compounds or trimethylsilylated diamines.

[0127] In addition, by using a silicon-atom-containing diamine such as 1,3-bis(3-aminopropyl)tetramethyldisiloxane or 1,3-bis(4-anilino)tetramethyldisiloxane as a diamine component, it is possible to improve adhesion to a substrate and resistance to oxygen plasma or UV ozone treatment used for cleaning, etc. These silicon-atom-containing diamines are preferably used in an amount of 1 to 30 mol% of the total diamine components.

[0128] In addition, preferably utilize monoamine, anhydride, acyl chloride or monocarboxylic acid with hydroxyl, carboxyl, sulfonic acid or thiol group to block the end of polyimide, polybenzoxazole, polyimide precursor, polybenzoxazole precursor.It is also possible to use more than 2 kinds of them.By having the aforementioned group at the resin end (for convenience, the group that the resin end is blocked is referred to as "end blocking group"), the dissolution rate of the resin in the alkaline aqueous solution can be easily adjusted to a preferred range.

[0129] Preferred examples of the monoamines include 5-amino-8-hydroxyquinoline, 1-hydroxy-7-aminonaphthalene, 1-hydroxy-6-aminonaphthalene, 1-hydroxy-5-aminonaphthalene, 1-hydroxy-4-aminonaphthalene, 2-hydroxy-7-aminonaphthalene, 2-hydroxy-6-aminonaphthalene, 2-hydroxy-5-aminonaphthalene, 1-carboxy-7-aminonaphthalene, 1-carboxy-6-aminonaphthalene, 1-carboxy-5-aminonaphthalene, 2-carboxy-7-aminonaphthalene, 2-carboxy- -6-aminonaphthalene, 2-carboxy-5-aminonaphthalene, 2-aminobenzoic acid, 3-aminobenzoic acid, 4-aminobenzoic acid, 4-aminosalicylic acid, 5-aminosalicylic acid, 6-aminosalicylic acid, 2-aminobenzenesulfonic acid, 3-aminobenzenesulfonic acid, 4-aminobenzenesulfonic acid, 3-amino-4,6-dihydroxypyrimidine, 2-aminophenol, 3-aminophenol, 4-aminophenol, 2-aminothiophenol, 3-aminothiophenol, 4-aminothiophenol, etc.

[0130] Preferred examples of the acid anhydride, monoacid chloride, monocarboxylic acid, and monoactive ester compound include phthalic anhydride, maleic anhydride, nadic acid, cyclohexanedicarboxylic anhydride, 3-hydroxyphthalic anhydride and the like, 3-carboxyphenol, 4-carboxyphenol, 3-carboxythiophenol, 4-carboxythiophenol, 1-hydroxy-7-carboxynaphthalene, 1-hydroxy-6-carboxynaphthalene, 1-hydroxy-5-carboxynaphthalene, 1-mercapto-7-carboxynaphthalene, 1-mercapto-6-carboxynaphthalene, 1-mercapto-5-carboxynaphthalene, 3-carboxybenzenesulfonic acid, 4-hydroxy- -Carboxybenzenesulfonic acid and other monocarboxylic acids and their carboxyl groups are chlorinated monoacyl chloride compounds, terephthalic acid, phthalic acid, maleic acid, cyclohexanedicarboxylic acid, 1,5-dicarboxynaphthalene, 1,6-dicarboxynaphthalene, 1,7-dicarboxynaphthalene, 2,6-dicarboxynaphthalene and other dicarboxylic acids are chlorinated only one carboxyl group of the monoacyl chloride compounds, monoactive ester compounds obtained by the reaction of monoacyl chloride compounds with N-hydroxybenzotriazole, N-hydroxy-5-norbornene-2,3-dicarboximide, etc.

[0131] The content of the terminal blocking agent such as monoamine, acid anhydride, acid chloride, monocarboxylic acid is preferably in the range of 0.1 to 60 mol % of the input mole number of the acid component monomer constituting the acid residue or the diamine component monomer constituting the amine residue, and more preferably 5 to 50 mol %. By setting it within such a range, a resin composition having a moderate solution viscosity when applying the resin composition and excellent film properties can be obtained.

[0132] The resin may also have a polymerizable functional group at the terminal. Examples of the polymerizable functional group include an ethylenically unsaturated bond group, an acetylene group, a hydroxymethyl group, and an alkoxymethyl group.

[0133] The terminal blocking groups introduced into the resin can be easily detected by the following methods. For example, the resin introduced with the terminal blocking groups can be dissolved in an acidic solution to decompose the amine component and the acid component as the structural unit of the resin, and then the terminal blocking agent can be easily detected by gas chromatography (GC) and NMR. In addition, the terminal blocking agent can be directly detected by thermal decomposition gas chromatography (PGC), infrared spectroscopy and 13 The resin into which the terminal blocking agent was introduced was detected by CNMR spectroscopy.

[0134] In the present invention, as the resin having an alkali-soluble group, a polyimide precursor or a polybenzoxazole precursor is preferably used, and a polyimide precursor is more preferably used. The polyimide precursor undergoes an imidization reaction of amic acid site ring closure by curing and firing at about 200°C, and the polybenzoxazole precursor undergoes an oxazolization reaction of hydroxyamide site ring closure by curing and firing at about 300°C, and a display device with high reliability can be obtained. Thus, the polyimide precursor can obtain a display device with high reliability at a lower firing temperature. In addition, for a photosensitive resin composition using these precursor resins having the property of volume shrinkage during curing and firing, after obtaining a fine pattern by an exposure and development process, firing is performed, thereby obtaining a pattern of a tapered shape. When the tapered shape pattern is used as an insulating film of an organic EL element, the coating property of the upper electrode is excellent, and disconnection can be prevented, thereby improving the reliability of the element.

[0135] <Compound Having an Alkali-Soluble Group>

[0136] In the present invention, resin composition A and resin composition B may contain a compound having an alkali-soluble group. Here, the meaning of alkali-soluble is the meaning described in the aforementioned resin having an alkali-soluble group. In addition, the description of the functional group used to make the compound have alkali solubility is also cited in the description of the aforementioned resin having an alkali-soluble group. It should be noted that, here, with respect to the compound having an alkali-soluble group, for the purpose of distinguishing it from the aforementioned resin having an alkali-soluble group, it refers to a compound having a molecular weight of less than 1000, and the resin having an alkali-soluble group refers to a resin having a molecular weight greater than 1000. As the molecular weight of the compound having an alkali-soluble group, from the viewpoint of developing adhesion, it is preferably more than 100. Furthermore, if it is more than 250, the developing adhesion is further improved. On the other hand, from the viewpoint of improving sensitivity, it is preferably less than 600, and more preferably less than 450.

[0137] As the compound having an alkali-soluble group, a compound having a phenolic hydroxyl group is preferred, and specific examples thereof include Bis-Z, BisOC-Z, BisOPP-Z, BisP-CP, Bis26X-Z, BisOTBP-Z, BisOCHP-Z, BisOCR-CP, BisP-PZ, BisCRIP Z, BisOCP-IPZ, BisOIPP-CP, Bis26X-IPZ, BisOTBP-CP, TekP-4HBPA (Tetrakis P-DO-BPA), TrisPHAP, TrisP-PA, TrisP-PHBA, TrisOCR-PA, BisOFP-Z, Bis25X-OCHP, BisOCHP-OC, Methylene Tris-FR-CR, BisRS-26X, BisRS-OCHP (trade names, manufactured by Honshu Chemical Industry Co., Ltd.), BIR-OC, BIP-PC, BIR-PC, BIR-PCHP, BIP-BIOC-F, 4PC, BIR-BIPC-F, TEP-BIP-A (trade names, manufactured by Asahi Organic Materials Industries Co., Ltd.), 1,4-dihydroxynaphthalene, 1,5-dihydroxynaphthalene, 2,4-dihydroxyquinoline, 2,6-dihydroxyquinoline, 2,3-dihydroxyquinoxaline, anthracene-1,2,10-triol, anthracene-1,8,9-triol, 8-hydroxyquinoline, catechol, etc.

[0138] Regarding the content in the resin composition when using a compound having a phenolic hydroxyl group as the compound having an alkali-soluble group, when the total weight of the above-mentioned resin is set to 100 parts by weight, from the viewpoint of improving sensitivity, it is preferably set to 1 part by weight or more. Furthermore, if it is 5 parts by weight or more, the sensitivity is further improved. On the other hand, from the viewpoint of developing adhesion, it is preferably 30 parts by weight or less, and more preferably 20 parts by weight or less.

[0139] <Protective Group Removable by Acid>

[0140] In the present invention, the resin composition A and the resin composition B contain the resin (A-1) or the compound (A-2). In addition, the resin composition A may contain the compound (A-2).

[0141] In the case of resin (A-1), all or part of the alkali-soluble groups of the aforementioned resin having alkali-soluble groups are protected by a protecting group that can be removed by acid, and in the case of compound (A-2), all or part of the alkali-soluble groups of the aforementioned compound having alkali-soluble groups are protected by a protecting group that can be removed by acid.

[0142] In the present invention, since a resin composition containing resin (A-1) or compound (A-2) is used, the acid generated by the photoacid generator (B) described later is used as a catalyst when the resin composition used to form a planarization layer or a pixel segmentation layer of an organic EL display device is exposed, and the protective group is detached, the alkali solubility of the exposed part is improved, and the sensitivity can be improved. Examples of such protective groups include acetal groups, ketal groups, silyl groups, silyl ether groups, and tetrahydropyranyloxy groups.

[0143] As the protecting group that can utilize acid to be separated, for example, tert-butoxycarbonyl, isopropoxycarbonyl, tetrahydropyranyl, ethoxyethyl, methoxyethyl, ethoxymethyl, trimethylsilyl, tert-butoxycarbonylmethyl, ethyl vinyl ether, methyl vinyl ether, trimethylsilyl ether etc. can be mentioned. It is also possible to contain two or more of them. From the viewpoint of improving sensitivity, it is preferably one or more groups selected from the group consisting of acetal group and ketal group.

[0144] These protecting groups can be easily introduced, for example, by reacting a vinyl ether compound with a compound having a phenolic hydroxyl group or a carboxyl group in the presence of an acid catalyst. Alternatively, they can be easily introduced by reacting a chloride of the protecting group to be introduced in the presence of a base catalyst such as an amine.

[0145] The protective group introduced into the alkali-soluble group and capable of being detached by acid can be easily detected by the following method. For example, the detection can be performed by the following method: the cured film is thermally decomposed under the condition of a heating temperature of 600°C using Multi Shot Pyrolyzer PY-3030D (manufactured by Frontier Lab), and a gas chromatograph mass spectrometer JMS-Q1050GC (manufactured by JEOL) is used, and the GC column uses a stainless steel capillary column (0.25 mm inner diameter × 30 m, stationary phase; 5% phenyl polydimethylsiloxane), the GC temperature is raised from 40°C (maintained for 3 minutes) to 320°C at a rate of 20°C / min, the injection port temperature is 300°C, the column flow rate is 1.5 mL / min, the ionization method is the EI (electron ionization) method, the mass number range is 10 to 800 in terms of m / z, and the scanning speed is set to 0.5 sec / scan for analysis.

[0146] In addition, in the above-mentioned resin composition A and resin composition B, when the weight of all resin components is set to 100 parts by weight, the content of compound (A-2) is preferably from 1 part by weight to 30 parts by weight, because it can further improve the reliability of the organic EL display device.

[0147] <(B) Photoacid Generator>

[0148] In the present invention, resin composition A and resin composition B contain (B) a photoacid generator (hereinafter, sometimes referred to as "component (B)"). Since resin composition A and resin composition B contain component (B), the protective group of resin (A-1) or compound (A-2) is detached during exposure, and the sensitivity is improved. It should be noted that component (B) does not contain a naphthoquinonediazide compound.

[0149] (B) The photoacid generator includes, for example, SI-100, SI-101, SI-105, SI-106, SI-109, SI-200, SI-210, PI-105, PI-106, PI-109, NAI-100, NAI-1002, NAI-1003, NAI-1004, NAI-101, NAI-105, NAI-106, NAI-109, NDI-101, NDI-105, NDI-106, NDI-109, PAI-01, PAI-101, PAI-106 or PAI-1001 (Midori Kagaku Co., Ltd.), SP-077, SP-082, SP-601, SP-606, SP-607 or SP-612 (manufactured by ADEKA Corporation), TPS-PFBS (manufactured by Toyo Gosei Kogyo Co., Ltd.), CGI-MDT or CGI-NIT (manufactured by Ciba Japan (co., Ltd.) WPAG-281, WPAG-336, WPAG-339, WPAG-342, WPAG-344, WPAG-350, WPAG-370, WPAG-372, WPAG-449, WPAG-469, WPAG-505 or WPAG-506 (Wako Pure Chemical Industries, Ltd.), PAG-103, PAG-121 or PAG-203 (BASF (co., Ltd.), MDT, NIT, MIN, ILP-110, ILP-110N, ILP-113, ILP-118, PA-223, PA298, PA-411, PA-480 or PA-528 (Heraeus (co., Ltd.)), etc. Two or more of them may be used. Among them, from the viewpoint of improving sensitivity, it is preferred to use one or more photoacid generators selected from the group consisting of oxime sulfonate photoacid generators, onium salt photoacid generators, and naphthalimide photoacid generators. Among them, it is preferred to use oxime sulfonate photoacid generators.

[0150] In the above-mentioned resin composition A and resin composition B, when the weight of all resin components is set to 100 parts by weight, from the viewpoint of improving sensitivity, the content of the photoacid generator (B) is preferably 0.1 parts by weight or more. Furthermore, if it is 2 parts by weight or more, the sensitivity is further improved. On the other hand, from the viewpoint of storage stability, it is preferably 30 parts by weight or less, and more preferably 20 parts by weight or less.

[0151] <Sensitizer>

[0152] The resin composition A and the resin composition B are preferably resin compositions further containing a sensitizer. By using the resin composition containing a sensitizer, the acid generation efficiency of the component (B) is improved, and the sensitivity is improved.

[0153] As a sensitizer, preferably (C) a thioxanthone or anthracene compound, for example, 2,4-dichlorothioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2-isopropylthioxanthone, 4-isopropylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, 1-chloro-4-propylthioxanthone, thioxanthone, 2-ethylthioxanthone, diethoxyanthracene, dipropoxyanthracene, dibutoxyanthracene, etc. can be mentioned. It is also possible to contain two or more of them. From the viewpoint of improving sensitivity, anthracene compounds are more preferably used.

[0154] In the resin composition that is the raw material of the cured film constituting the planarization layer or the pixel segmentation layer, when all the resin components contained in the resin composition are set to 100 parts by weight, from the viewpoint of improving sensitivity, the content of the sensitizer is preferably 0.1 parts by weight or more. Furthermore, if it is 1 part by weight or more, the sensitivity is further improved. On the other hand, from the viewpoint of storage stability, it is preferably 10 parts by weight or less, and more preferably 5 parts by weight or less.

[0155] <Quinonediazide compounds>

[0156] The above-mentioned resin composition A and resin composition B may also contain quinonediazide compounds. As quinonediazide compounds, compounds obtained by bonding quinonediazide sulfonic acid with polyhydroxy compounds in the form of esters, compounds obtained by bonding quinonediazide sulfonic acid with polyamino compounds by sulfonamide bonds, compounds obtained by bonding quinonediazide sulfonic acid with polyhydroxy polyamino compounds by ester bonds and / or sulfonamide bonds, etc. can be cited. As such compounds, naphthoquinonediazide is commonly used. From the perspective of the contrast between the exposed portion and the unexposed portion, it is preferred that more than 50 mol% of the functional groups of these polyhydroxy compounds and polyamino compounds as a whole are substituted by quinonediazide groups. By using such quinonediazide compounds, a positive photosensitive resin composition that is sensitive to the i-line (365nm), h-line (405nm), and g-line (436nm) of a mercury lamp as a common ultraviolet light can be obtained.

[0157] Examples of the polyhydroxy compound include Bis-Z, BisP-EZ, TekP-4HBPA, TrisP-HAP, TrisP-PA, TrisP-SA, TrisOCR-PA, BisOCHP-Z, BisP-MZ, BisP-PZ, BisP-IPZ, BisOCP-IPZ, BisP-CP, BisRS-2P, BisRS-3P, BisP-OCHP, MethyleneTris-FR-CR, BisRS-26X, DML-MBPC, DML-MBOC, DML-OCHP, DML-PCHP, DML-PC, DML-PTBP, DML-34X, DML-EP, DML-POP, Dimethylol-BisOC-P, DMLPFP, DML-PSBP, DML-MTrisPC, TriML-P, TriML-35XL, TML-BP, and TM L-HQ, TML-pp-BPF, TML-BPA, TMOM-BP, HML-TPPHBA, HM L-TPHAP (these are trade names, manufactured by Honshu Chemical Industry Co., Ltd.), BIR-OC, BIP-PC, BIR-PC, BIR-PTBP, BIR-PCHP, BIP-BIOC-F, 4PC, BIR-BIPC-F, TEP-BIP-A, 46DMOC, 46DMOEP, TM-BIP-A (these are trade names, manufactured by Asahi Organic Materials Industries, Ltd.), 2,6-dimethoxymethyl-4-tert-butylphenol, 2,6-dimethoxymethyl-p-cresol, 2,6-diacetoxymethyl-p-cresol, naphthol, tetrahydroxybenzophenone, methyl gallate, bisphenol A, bisphenol E, methylene bisphenol, Bis P-AP (trade name, manufactured by Honshu Chemical Industry Co., Ltd.), etc., but are not limited to these.

[0158] Examples of the polyamino compound include 1,4-phenylenediamine, 1,3-phenylenediamine, 4,4′-diaminodiphenyl ether, 4,4′-diaminodiphenylmethane, 4,4′-diaminodiphenyl sulfone, and 4,4′-diaminodiphenyl ether, but are not limited thereto.

[0159] Examples of the polyhydroxypolyamino compound include 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane and 3,3′-dihydroxybenzidine, but are not limited thereto.

[0160] In the present invention, the quinonediazide group can preferably be any of naphthoquinonediazide-5-sulfonyl group and naphthoquinonediazide-4-sulfonyl group. In addition, naphthoquinonediazide sulfonate compounds having naphthoquinonediazide-4-sulfonyl group and naphthoquinonediazide-5-sulfonyl group in the same molecule can be used, and naphthoquinonediazide-4-sulfonate compounds and naphthoquinonediazide-5-sulfonate compounds can also be used in combination.

[0161] Examples of a method for synthesizing the naphthoquinonediazide compound used in the present invention include a method of reacting naphthoquinonediazide-5-sulfonyl chloride with a polyhydroxy compound in the presence of triethylamine.

[0162] In the above-mentioned resin composition A and resin composition B, when the weight of all resin components is set to 100 parts by weight, from the viewpoint of improving sensitivity, the content of the naphthoquinonediazide compound is preferably 2 parts by weight or more. Furthermore, if it is 5 parts by weight or more, the sensitivity is further improved. On the other hand, from the viewpoint of storage stability, it is preferably 40 parts by weight or less, and more preferably 35 parts by weight or less.

[0163] <Thermal crosslinking agent>

[0164] The resin composition A and the resin composition B may further contain a thermal crosslinking agent.

[0165] The so-called thermal crosslinking agent refers to a compound having at least two thermally reactive functional groups represented by alkoxymethyl, hydroxymethyl, epoxy, and oxetanyl in the molecule. The thermal crosslinking agent can improve the heat resistance, chemical resistance, and hardness of the film after thermal curing.

[0166] Preferred examples of the compound having at least two alkoxymethyl groups or hydroxymethyl groups include DML-PC, DML-PEP, DMOM-PC, TriML-P, TriML-35XL, TML-HQ, TML-BP, TML-pp-BPF, TML-BPE, TMOM-BP, TMOM-BPE, TMOM-BPA, TMOM-BPAF, TMOM-BPAP, HML-TP PHBA, HML-TPHAP, HMOM-TPPHBA, HMOM-TPHAP (these are trade names, manufactured by Honshu Chemical Industry Co., Ltd.), NIKALAC (registered trademark) MX-290, NIKALAC MX-280, NIKALAC MX-270, NIKALAC MW-100LM, and NIKALAC MX-750LM (these are trade names, manufactured by Sanwa Chemical Co., Ltd.), each of which can be obtained from the aforementioned companies.

[0167] Examples of the compound having an epoxy group or an oxetanyl group, and examples of the compound having two epoxy groups in one molecule include "Epikote" (registered trademark) 807, "Epikote" 828, "Epikote" 1002, "Epikote" 1750, "Epikote" 1007, YX 8100-BH30, E1256, E4250, E4275 (these are trade names, manufactured by Japan Epoxy Co., Ltd.), "Epiclon" (registered trademark) EXA-4880, "Epiclon" EXA-4822, "Epiclon" EXA-9583, HP4032 (these are trade names, manufactured by Dainippon Ink & Chemicals Co., Ltd.), "EPOLIGHT" (registered trademark) 40E, "EPO LIGHT" 100E, "EPOLIGHT" 200E, "EPOLIGHT" 400E, "EPOLIGHT" "OLIGHT" 70P, "EPOLIGHT" 200P (these are trade names, manufactured by Kyoeisha Chemical Co., Ltd.), "Denacol" (registered trademark) EX-212L, "Denacol" EX-214L, "Denacol" EX-216L (these are trade names, manufactured by Nagase Chemtex Co., Ltd.), GAN, GOT (these are trade names, manufactured by Nippon Kayaku Co., Ltd.), etc., can be obtained from each company.

[0168] Examples of the compound having three or more epoxy groups include VG3101L (trade name, manufactured by Printec Corporation), “TEPIC” (registered trademark) S, “TEPIC” G, “TEPIC” P (these are trade names, manufactured by Nissan Chemical Industries, Ltd.), “Epiclon” N660, “Epiclon” N695, HP7200 (these are trade names, manufactured by Dainippon Ink & Chemicals Co., Ltd.), “Denacol” EX-321L (trade name, manufactured by Nagase Chemtex Co., Ltd.), NC6000, EPPN502H, NC3000 (these are trade names, manufactured by Nippon Kayaku Co., Ltd.), “Epotohto” (registered trademark) YH-434L (trade name, manufactured by Tohto Kasei Co., Ltd.), EHPE-3150 (trade name, manufactured by DAI As the compound having two or more oxetane groups, OXT-121, OXT-221, OX-SQ-H, OXT-191, PNOX-1009, RSOX (the above are trade names, manufactured by Toagosei Co., Ltd.), "ETERNACOLL" (registered trademark) OXBP, "ETERNACOLL" OXTP (the above are trade names, manufactured by Ube Industries, Ltd.), etc. can be cited, each of which can be obtained from each company.

[0169] In the above-mentioned resin composition A and resin composition B, when the weight of all resin components is set to 100 parts by weight, if the content of the thermal crosslinking agent is more than 5 parts by weight, the crosslinking density of the cured product becomes high, and the chemical resistance is improved, so it is preferred. And then, if it is more than 10 parts by weight, higher mechanical properties can be obtained. On the other hand, from the viewpoint of storage stability and mechanical strength, it is preferably less than 50 parts by weight, more preferably less than 40 parts by weight, and further preferably less than 30 parts by weight.

[0170] Aforementioned resin combination A and resin combination B can also contain close fit improver, can assist close fit after developing, improve close fit after curing.As close fit improver, can enumerate silane coupling agents such as vinyl trimethoxy silane, vinyl triethoxy silane, epoxy cyclohexyl ethyl trimethoxy silane, 3-glycidoxy propyl trimethoxy silane, 3-glycidoxy propyl triethoxy silane, p-phenylyl trimethoxy silane, 3-aminopropyl trimethoxy silane, 3-aminopropyl triethoxy silane, N-phenyl-3-aminopropyl trimethoxy silane, titanium chelate, aluminum chelate, make aromatic amine compound and the compound obtained by reacting the silicon compound containing alkoxy group etc.Also can use more than 2 kinds among them.

[0171] The resin composition A and the resin composition B may contain a surfactant to improve wettability with a substrate.

[0172] Examples of the surfactant include fluorine-based surfactants such as FLOURAD (trade name, manufactured by Sumitomo 3M Co., Ltd.), “MEGAFACE” (registered trademark) (trade name, manufactured by DIC Corporation), and “SURFLON” (registered trademark) (trade name, manufactured by AGC Seimi Chemical Co., Ltd.); organosiloxane surfactants such as KP341 (trade name, manufactured by Shin-Etsu Chemical Co., Ltd.), DBE (trade name, manufactured by Chisso Corporation), Glanol (trade name, manufactured by Kyoeisha Chemical Co., Ltd.), and BYK (manufactured by BYK Chemie Co., Ltd.); and acrylic polymer surfactants such as Polyflow (trade name, manufactured by Kyoeisha Chemical Co., Ltd.).

[0173] <Method for producing resin composition A and resin composition B>

[0174] A typical method for producing the resin composition A and the resin composition B is described below. The target resin composition can be obtained by mixing components selected from the alkali-soluble resin, the resin (A-1), the compound (A-2) and the component (B), and other additives and solvents used as needed, stirring for 20 minutes to 3 hours to prepare a uniform solution, and filtering the obtained solution after stirring.

[0175] <Method for manufacturing organic EL display device>

[0176] The manufacturing method of the organic EL display device of the present invention is described. The organic EL display device of the present invention can be obtained, for example, by the following method: forming TFT (thin film transistor) and wiring on a substrate, forming a planarization layer in a manner covering the concavo-convex on the substrate produced by them, forming a first electrode, a pixel segmentation layer and a light-emitting layer on the planarization layer, and further forming a second electrode. The planarization layer and the pixel segmentation layer can be formed, for example, by applying the aforementioned resin composition A or resin composition B, patterning by photolithography and curing it. In the case of an active matrix type, the second electrode is usually formed throughout the entire light-emitting area. After the second electrode is formed, it is preferably sealed. It is generally believed that organic EL display devices have weak resistance to oxygen and moisture. In order to obtain a display device with high reliability, it is preferably sealed in an atmosphere with as little oxygen and moisture as possible.

[0177] <Step of Patterning the First Electrode or the Second Electrode>

[0178] As a method of patterning the first electrode or the second electrode, for example, an etching method can be cited. Hereinafter, a method of patterning the first electrode by etching will be described as an example.

[0179] Preferably, after applying the material constituting the first electrode on the substrate, a photoresist is applied on the first electrode and pre-baked. Then, preferably, the photoresist is exposed and developed, thereby forming a pattern of the photoresist on the first electrode by photolithography. After development, the obtained pattern is preferably heat-treated. By performing the heat treatment, the chemical resistance and dry etching resistance are improved by thermal curing of the photoresist, so the pattern of the photoresist can be suitably used as an etching mask. As a heating treatment device, for example, an oven, a hot plate, infrared rays, a rapid annealing device, a laser annealing device, etc. can be cited. The heating treatment temperature is preferably 70 to 200°C, and the heating treatment time is preferably 30 seconds to several hours.

[0180] Next, preferably, the first electrode is patterned by etching using the photoresist pattern as an etching mask. Examples of the etching method include wet etching using an etching solution and dry etching using an etching gas.

[0181] Examples of the etching solution include acidic or alkaline etching solutions, organic solvents, etc. Two or more of these may be used.

[0182] After etching, the photoresist remaining on the first electrode is removed, thereby obtaining a pattern of the first electrode.

[0183] <Step of applying resin composition>

[0184] Examples of methods for applying the resin composition A or the resin composition B include micro gravure coating, spin coating, dip coating, curtain coating, roll coating, spray coating, slit coating, etc. In addition, examples of methods for applying the resin composition in a pattern include relief printing, gravure printing, stencil printing, lithography, screen printing, inkjet printing, offset printing, laser printing, etc.

[0185] The thickness of the coating film varies depending on the coating method, the solid content concentration of the resin composition, the viscosity, etc., but it is preferably applied so that the film thickness after coating and prebaking becomes 0.1 to 30 μm.

[0186] After applying the resin composition, it is preferably prebaked. As a heat treatment device for prebaking, for example, an oven, a hot plate, infrared rays, a rapid annealing device, a laser annealing device, etc. can be cited. The prebaking temperature is preferably 50 to 150°C, and the prebaking time is preferably 30 seconds to several hours. Prebaking can also be performed in multiple stages (prebaking at 80°C for 2 minutes and then prebaking at 120°C for 2 minutes, etc.) of more than two stages.

[0187] <Step of Patterning the Resin Composition Film>

[0188] As a method of patterning the planarization layer or the pixel division layer, processing by photolithography can be adopted from the viewpoint of improving productivity and shortening process time due to reduction in the number of steps.

[0189] For example, preferably, an exposure machine such as a stepper, a mirror projection mask aligner (MPA) or a parallel light mask aligner (PLA) is used to expose the pre-baked film of the resin composition formed by the above method. As active chemical rays irradiated during exposure, for example, ultraviolet rays, visible rays, electron beams, X-rays, KrF (wavelength 248nm) lasers, ArF (wavelength 193nm) lasers, etc. are mentioned. Preferably, the j-line (wavelength 313nm), i-line (wavelength 365nm), h-line (wavelength 405nm), and g-line (wavelength 436nm) of a mercury lamp are used. The exposure amount is generally 100 to 40,000 J / m 2 (10~4,000mJ / cm 2 ) (the value of the i-line illuminometer), and exposure can be performed through a mask having a desired pattern as needed.

[0190] After the exposure, it is preferably developed using an automatic developing device, etc. When the resin composition has positive photosensitivity, after the development, the exposed portion is removed by a developer, thereby obtaining a relief pattern.

[0191] As the developer, an alkaline developer or an organic solvent is generally used. As the alkaline developer, an organic alkaline solution or an aqueous solution of an alkaline compound is preferred, and from an environmental point of view, an aqueous solution of an alkaline compound, i.e., an alkaline aqueous solution, is more preferred.

[0192] Examples of the organic alkaline solution or the compound showing alkalinity include tetramethylammonium hydroxide and tetraethylammonium hydroxide.

[0193] As a developing method, for example, a method of applying a developer on the film after exposure is mentioned. The film after exposure is preferably in contact with the developer for 5 seconds to 10 minutes.

[0194] After development, the obtained relief pattern is preferably washed with a rinse liquid. When an alkaline aqueous solution is used as a developer, the rinse liquid is preferably water.

[0195] The resin film with the pattern formed thereon may also be subjected to bleaching exposure. By performing bleaching exposure, the shape of the pattern after curing can be arbitrarily adjusted. In addition, the transparency of the cured film can be improved.

[0196] <Step of Obtaining a Cured Product of the Resin Composition>

[0197] By curing the film of the resin composition after exposure and development, a planarization layer or a pixel segmentation layer can be formed. For curing, it is simple to adopt thermal curing. As the heating treatment device used, the device exemplified as a heating treatment device for pre-baking can be cited. By heating the pattern of the resin composition to thermally cure it, the heat resistance of the cured film can be improved, and a pattern with a low taper shape can be formed. It should be noted that the treatment of applying heat that does not require chemical changes to be caused by curing, but causes volatile components to fly or promotes molecular motion to achieve densification, is also included in the scope of the so-called "curing" in the present invention.

[0198] The thermal curing temperature is preferably 150° C. or higher, more preferably 250° C. or higher. If the thermal curing temperature is within the above range, the heat resistance of the cured film can be improved, and the pattern shape after thermal curing can be further reduced in taper. On the other hand, from the viewpoint of shortening the cycle time, the thermal curing temperature is preferably 500° C. or lower, more preferably 400° C. or lower.

[0199] The thermal curing time is preferably 1 minute or longer, and particularly preferably 30 minutes or longer. If the thermal curing time is within the above range, the pattern shape after thermal curing can be further reduced in taper.

[0200] <Production of Light Emitting Layer>

[0201] The light-emitting layer can be formed, for example, by mask evaporation or spraying. As a representative mask evaporation method, the following method can be cited, which is a method of patterning an organic compound by evaporating it using an evaporation mask, wherein the evaporation mask having the desired pattern as the opening is arranged on the evaporation source side of the substrate and evaporation is performed.

[0202] Example

[0203] The present invention will be described in more detail below with reference to Examples and Comparative Examples. However, it should not be understood that the present invention is limited to the Examples. It should be noted that the names of the compounds used for which abbreviations are used are shown below.

[0204] 4-MOP: 4-methoxyphenol

[0205] AIBN: 2,2'-azobis(isobutyronitrile)

[0206] BAHF: 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane

[0207] BFE: 1,2-bis(4-formylphenyl)ethane

[0208] DBA: dibenzylamine

[0209] DFA: N,N-dimethylformamide dimethyl acetal

[0210] GMA: Glycidyl Methacrylate

[0211] MAA: Methacrylic acid

[0212] MAP: 3-aminophenol; m-aminophenol

[0213] NMP: N-methyl-2-pyrrolidone

[0214] ODPA: Bis(3,4-dicarboxyphenyl)ether dianhydride; Oxydiphthalic anhydride

[0215] NA: Nadic anhydride

[0216] PGMEA: Propylene glycol monomethyl ether acetate

[0217] SiDA: 1,3-bis(3-aminopropyl)tetramethyldisiloxane

[0218] STR: Styrene

[0219] TCDM: tricyclic methacrylate [5.2.1.0 2,6 ]Decan-8-yl ester; dihydroxymethyl-tricyclodecane dimethacrylate.

[0220] Synthesis Example 1 Synthesis of polyimide precursor (PI-1)

[0221] Under a dry nitrogen stream, 31.02 g of ODPA (0.10 mol; 100 mol% relative to the structural units derived from all carboxylic acids and their derivatives) and 150 g of NMP were weighed and dissolved in a three-necked flask. A solution obtained by dissolving 25.64 g of BAHF (0.070 mol; 56.0 mol% relative to the structural units derived from all amines and their derivatives) and 1.24 g of SiDA (0.0050 mol; 4.0 mol% relative to the structural units derived from all amines and their derivatives) in 50 g of NMP was added thereto, and the mixture was stirred at 20° C. for 1 hour and then at 50° C. for 2 hours. Next, as a terminal blocking agent, a solution obtained by dissolving 5.46 g of MAP (0.050 mol; 40.0 mol% relative to the structural units derived from all amines and their derivatives) in 15 g of NMP was added, and the mixture was stirred at 50° C. for 2 hours. Then, a solution obtained by dissolving 23.83g (0.20mol) of DFA in 15g of NMP was added dropwise over 10 minutes. After the addition was completed, it was stirred at 50°C for 3 hours. After the reaction was completed, the reaction solution was cooled to room temperature, and then the reaction solution was put into 3L of water, and the precipitated solid was filtered out. After washing the obtained solid with water 3 times, it was dried for 24 hours in a vacuum dryer at 80°C to obtain a polyimide precursor (PI-1). The weight average molecular weight (Mw) of the obtained polyimide precursor (PI-1) was 20,000.

[0222] Synthesis Example 2 Synthesis of polybenzoxazole precursor (PBO-1)

[0223] In a 500 mL round-bottom flask equipped with a Dean-Stark water separator filled with toluene and a condenser, 34.79 g of BAHF (0.095 mol; 95.0 mol% relative to the structural units derived from all amines and their derivatives), 1.24 g of SiDA (0.0050 mol; 5.0 mol% relative to the structural units derived from all amines and their derivatives), and 70.00 g of NMP were weighed and dissolved. A solution obtained by dissolving 19.06 g of BFE (0.080 mol; 66.7 mol% relative to the structural units derived from all carboxylic acids and their derivatives) in 20.00 g of NMP was added thereto, and the mixture was stirred at 20° C. for 1 hour and then at 50° C. for 2 hours. Next, as a terminal blocking agent, a solution obtained by dissolving 6.57 g of NA (0.040 mol; 33.3 mol% relative to the structural units derived from all carboxylic acids and their derivatives) in 10 g of NMP was added, and the mixture was stirred at 50° C. for 2 hours. Then, under a nitrogen atmosphere, the mixture was stirred at 100°C for 2 hours. After the reaction was completed, the reaction solution was added to 3L of water and filtered to obtain the precipitated solid. The obtained solid was washed with water 3 times, and then dried in a vacuum dryer at 80°C for 24 hours. After washing with water 3 times, the mixture was dried in a vacuum dryer at 80°C for 24 hours to obtain a polybenzoxazole precursor (PBO-1). The Mw of the obtained polybenzoxazole precursor (PBO-1) was 20,000.

[0224] Synthesis Example 3 Synthesis of acrylic resin (AC-1)

[0225] A three-necked flask was charged with 0.821 g (1 mol%) of AIBN and 29.29 g of PGMEA. Then, 21.52 g (50 mol%) of MAA, 22.03 g (20 mol%) of TCDM, and 15.62 g (30 mol%) of STR were charged, and the mixture was briefly stirred at room temperature. After nitrogen was fully replaced in the flask by bubbling, the mixture was stirred at 70°C for 5 hours. Next, a solution obtained by dissolving 14.22 g (20 mol%) of GMA, 0.676 g (1 mol%) of DBA, and 0.186 g (0.3 mol%) of 4-MOP in 59.47 g of PGMEA was added to the obtained solution, and the mixture was stirred at 90°C for 4 hours to obtain a solution of acrylic resin (AC-1). The Mw of the obtained acrylic resin (AC-1) was 15,000.

[0226] Synthesis Example 4 Synthesis of a polyimide precursor (PIP-1) in which an alkali-soluble group is protected by a protecting group

[0227] The polyimide precursor (PI-1) 10g and PGMEA 18.2g obtained in Synthesis Example 1 were weighed in a three-necked flask and dissolved. Ethyl vinyl ether 5.38g (74.6mmol) and pyridinium p-toluenesulfonate 1.88g (7.46mmol) were added thereto and stirred at room temperature for 14 hours. Next, 30mL of ultrapure water was added and purification based on liquid separation operation was performed 3 times. Then, molecular sieves were added and dried for 12 hours. The protection rate of the alkali-soluble group of the protected polyimide precursor (PIP-1) recovered in the form of PGMEA solution was 33%, and the solid content concentration of the PGMEA solution of the protected polyimide precursor (PIP-1) was 24% by mass. It should be noted that the so-called protection rate is the ratio of the number of alkali-soluble groups protected by the protecting group to the number of all alkali-soluble groups before protection with the protecting group.

[0228] Synthesis Example 5 Synthesis of polybenzoxazole precursor (PBOP-1) in which the alkali-soluble group is protected by a protecting group

[0229] In a three-necked flask, 10 g of the polybenzoxazole precursor (PBO-1) obtained in Synthesis Example 2 and 18.2 g of PGMEA were weighed and dissolved. 5.38 g (74.6 mmol) of ethyl vinyl ether and 1.88 g (7.46 mmol) of pyridinium p-toluenesulfonate were added thereto and stirred at room temperature for 14 hours. Next, 30 mL of ultrapure water was added and purified based on liquid separation operation three times. Then, molecular sieves were added and dried for 12 hours. The protection rate of the alkali-soluble group of the protected polybenzoxazole precursor (PBOP-1) recovered in the form of a PGMEA solution was 33%, and the solid content concentration of the PGMEA solution of the protected polybenzoxazole precursor (PBOP-1) was 24% by mass.

[0230] Synthesis Example 6 Synthesis of acrylic resin (ACP-1) in which alkali-soluble groups are protected by protecting groups

[0231] In a three-necked flask, 10 g of the acrylic resin (AC-1) obtained in Synthesis Example 3 and 18.2 g of PGMEA were weighed and dissolved. 5.38 g (74.6 mmol) of ethyl vinyl ether and 1.88 g (7.46 mmol) of pyridinium p-toluenesulfonate were added thereto, and stirred at room temperature for 14 hours. Next, 30 mL of ultrapure water was added, and purification based on liquid separation operation was performed three times. Then, molecular sieves were added and dried for 12 hours. The protection rate of the alkali-soluble group of the protected acrylic resin (ACP-1) recovered in the form of a PGMEA solution was 33%, and the solid content concentration of the PGMEA solution of the protected acrylic resin (ACP-1) was 24% by mass.

[0232] Synthesis Example 7 Synthesis of a polyimide precursor (PIP-2) in which the alkali-soluble group is protected by a protecting group

[0233] In a three-necked flask, 10 g of the polyimide precursor (PI-1) obtained in Synthesis Example 1 and 18.2 g of pyridine were weighed and dissolved. 1.28 g (5.9 mmol) of di-tert-butyl dicarbonate was added thereto and stirred at room temperature for 3 hours. Then, the mixture was added to a solution of 1 L of ultrapure water and 20 g of concentrated hydrochloric acid. The precipitated powder was filtered and washed with water. The protection rate of the alkali-soluble group of the recovered protected polyimide precursor (PIP-2) was 33%.

[0234] Synthesis Example 8 Synthesis of a Compound Having a Phenolic Hydroxyl Group in Which an Alkali-Soluble Group is Protected by a Protecting Group (TPPA-1)

[0235] In a three-necked flask, 10 g of TrisP-PA (trade name, Honshu Chemical Industry Co., Ltd.) and 28.3 g of PGMEA were weighed and dissolved. 3.88 g (53.8 mmol) of ethyl vinyl ether and 1.35 g (5.38 mmol) of pyridinium p-toluenesulfonate were added thereto, and the mixture was stirred at room temperature for 24 hours. Next, 30 mL of ultrapure water was added, and purification based on liquid separation operation was performed three times. Then, molecular sieves were added and dried for 12 hours. The protection rate of the alkali-soluble groups of the protected phenolic low molecular weight (TPPA-1) recovered in the form of a PGMEA solution was 33%, and the solid content concentration of the PGMEA solution of the protected phenolic low molecular weight (TPPA-1) was 24% by mass.

[0236] Synthesis Example 8 Synthesis of Protected Phenolic Low Molecular Weight Compound (TEKP-1)

[0237] In a three-necked flask, 10 g of TekP-4HBPA (trade name, Honshu Chemical Industry Co., Ltd.) and 28.3 g of PGMEA were weighed and dissolved. 3.88 g (53.8 mmol) of ethyl vinyl ether and 1.35 g (5.38 mmol) of pyridinium p-toluenesulfonate were added thereto, and stirred at room temperature for 24 hours. Next, 30 mL of ultrapure water was added, and purification based on liquid separation operation was performed three times. Then, molecular sieves were added and dried for 12 hours. The protection rate of the alkali-soluble groups of the protected phenolic low molecular weight (TEKP-1) recovered in the form of a PGMEA solution was 33%, and the solid content concentration of the PGMEA solution of the protected phenolic low molecular weight (TEKP-1) was 24% by mass.

[0238] Synthesis Example 9 Synthesis of a Compound Having a Phenolic Hydroxyl Group in Which an Alkali-Soluble Group is Protected by a Protecting Group (CATE-1)

[0239] Weigh 10g of catechol and 28.3g of PGMEA in a three-necked flask and dissolve them. Add 10.17g (141.0mmol) of ethyl vinyl ether and 3.54g (14.10mmol) of pyridinium p-toluenesulfonate thereto, and stir at room temperature for 24 hours. Next, add 30mL of ultrapure water and perform purification based on liquid separation operation 3 times. Then, add molecular sieves and dry for 12 hours. The protection rate of the alkali-soluble group of the protected phenolic low molecular weight (CAT E-1) recovered in the form of PGMEA solution is 33%, and the solid content concentration of the PGMEA solution of the protected phenolic low molecular weight (CATE-1) is 24% by mass.

[0240] The characteristics evaluation in each of the examples and comparative examples was performed by the following methods.

[0241] (1) Sensitivity evaluation

[0242] The resin composition was applied to an 8-inch silicon wafer by spin coating using a coating and developing device ACT-8 (manufactured by Tokyo Electron Limited), and baked at 120° C. for 3 minutes using a hot plate to prepare a pre-baked film with a film thickness of 3.0 μm. It should be noted that the film thickness was measured using Lambda Ace STM-602 manufactured by Dainippon Screen Mfg. Co., Ltd. under the condition of a refractive index of 1.63.

[0243] Then, an exposure machine i-line stepper NSR-2005i9C (manufactured by Nikon Corporation) was used to expose the film at 50 to 300 mJ / cm through a mask having a pattern of contact holes of 10 μm. 2 The exposure dose is 10mJ / cm 2 After exposure, the film was developed using the aforementioned ACT-8 developing device with a 2.38 mass % tetramethylammonium (TMAH) aqueous solution (manufactured by Tama Chemical Industry Co., Ltd.) for a time period until the film loss during development reached 0.5 μm, and then rinsed with distilled water and spun dry to obtain a pattern.

[0244] The pattern of the developed film was observed at a magnification of 20 times using an FDP microscope MX61 (manufactured by Olympus Corporation) to determine the minimum exposure required for the opening diameter of the contact hole to be 10 μm. This was taken as the exposure sensitivity, and 200 mJ / cm 2 The smaller the value of the sensitivity is, the higher the sensitivity is, and the more preferred it is.

[0245] (2) Bending resistance evaluation

[0246] The resin composition was applied to a polyimide film substrate by spin coating, and pre-baked on a hot plate at 120° C. for 2 minutes as a drying process to obtain a resin film. Next, an automatic developing device (AD-2000 manufactured by Takizawa Sangyo Co., Ltd.) was used to perform spray development for 90 seconds using a 2.38 mass % tetramethylammonium hydroxide aqueous solution, followed by rinsing with pure water for 30 seconds. The developed substrate with a positive photosensitive resin film was cured (heat treated) in a nitrogen atmosphere at 250° C. in an oven for 60 minutes to obtain a cured product with a film thickness of 2.0 μm.

[0247] Next, the polyimide film substrate with the cured product was cut into 10 sheets with a length of 50 mm and a width of 10 mm. Next, the cut polyimide film substrate was stored in an air atmosphere at 100°C for 500 hours. Then, the surface on one side with the cured product was made to be the outside, and in the longitudinal central part, the interval of the bent substrate was kept at a predetermined interval and the shape of the bent portion was kept in a semicircular shape, and it was bent at 180° and kept in the bent state for 30 seconds. After 30 seconds, the bent polyimide film substrate was unfolded, and the surface of the cured product near the bent portion was observed using an FPD inspection microscope (MX-61L; manufactured by Olympus Corporation), and the appearance changes of the cured product surface were evaluated. The bending test was carried out in a range of a curvature radius of 0.1 to 2.0 mm, and the minimum curvature radius (mm) at which no appearance changes such as cracks occurred on the surface of the cured product were recorded. The smaller the value of the minimum curvature radius (mm), the higher the bending resistance, which is more preferred.

[0248] (3) Heat resistance evaluation

[0249] Using a coating and developing device ACT-8 (manufactured by Tokyo Electron Limited), the resin composition was applied to an 8-inch silicon wafer by spin coating, and baked at 120°C using a hot plate for 3 minutes to produce a pre-baked film with a film thickness of 3.0 μm. Then, using the aforementioned ACT-8 developing device, a 2.38% by mass TMAH aqueous solution was used to develop the film until the film loss during development became 0.5 μm, then rinsed with distilled water and then dried. Then, using an inert oven (CLH-21CD-S manufactured by KoyoThermo Systems Co., Ltd.), the film was cured in an oven at 250°C under a nitrogen atmosphere for 60 minutes. The obtained cured film was peeled off using hydrofluoric acid to obtain a film. 10 mg of the obtained single-film membrane piece was loaded into an aluminum fixture unit to prepare a sample for measurement based on TGA. Using TGA-50 (manufactured by Shimadzu Corporation), a thermogravimetric measurement was performed while heating at 10°C per minute under a nitrogen atmosphere. The temperature at which the weight is reduced by 5% compared to the weight at 200° C. is determined. The case where the temperature is 320° C. or higher is considered acceptable. The higher the temperature at which the weight is reduced by 5% compared to the weight at 200° C., the higher the heat resistance is, and the more preferable it is.

[0250] (4) Evaluation of Development Adhesion

[0251] Using a coating and developing device ACT-8 (manufactured by Tokyo Electron Limited), the resin composition was applied to an 8-inch silicon wafer by spin coating, and baked on a hot plate at 120°C for 3 minutes to produce a pre-baked film with a film thickness of 3.0 μm. It should be noted that the film thickness was measured using Lambda Ace STM-602 manufactured by Dainippon Screen Mfg. Co., Ltd. under the condition of a refractive index of 1.63. Then, using an exposure machine i-line stepper NSR-2005i9C (manufactured by Nikon Corporation), exposure was performed using an exposure amount of the exposure sensitivity calculated in (1) through a mask having a plurality of shading portions formed by a square pattern with a side of 3 to 100 μm. It should be noted that a test mask (test mask) was used in which the length between adjacent shading portions and opening portions was the same and the length was 3 to 100 μm. After exposure, the film was developed using a 2.38 mass % TMAH aqueous solution using the aforementioned ACT-8 developing device for a time period until the film loss during development reached 0.5 μm, and then rinsed with distilled water and dried to obtain a pattern.

[0252] The pattern of the developed film was observed at 20 times magnification using an FDP microscope MX61 (manufactured by Olympus Corporation), and 100 locations were observed for each size to find the smallest light-shielding pattern in which 90 or more patterns remained without peeling off. If the pattern of 10 μm or less remained without peeling off, it was considered to be acceptable.

[0253] (5) Amount of metal elements and halogen elements in the pixel segmentation layer

[0254] Into the pixel division layer of the organic EL display device, chloride ions and lithium ions were introduced at 3.5×10 14 Pieces / cm 2 , 1.2×10 14 Pieces / cm 2 The relative sensitivity factor (RSF) was calculated.

[0255] Based on the obtained relative sensitivity coefficient, the concentrations of metal elements and halogen elements (target elements) in the pixel division layer at about 0.5 μm from the layer surface were quantified by TOF-SIMS analysis using the following formula. TOF.SIMS5 manufactured by ION-TO F was used for TOF-SIMS analysis.

[0256] It should be noted that, regarding the concentration, for chlorine, it is converted based on the sensitivity in the pixel segmentation layer. For other elements whose secondary ion polarity is anion, the relative sensitivity coefficient for chlorine in the pixel segmentation layer is used for quantification. In addition, for other elements whose secondary ion polarity is cation, the relative sensitivity coefficient obtained in lithium in the pixel segmentation layer is corrected and quantified by the relative sensitivity coefficient ratio of lithium injected into the silicon wafer and each element obtained separately. Regarding the relative sensitivity coefficient, the values ​​recorded in App.E17~18 of Secondary Ion Mass Spectrometry: A Practical Handbook for Depth Profiling and Bulk Impurity Analysis (written by Robert G. Wilson. Fred A. Stevie. Charles W. Magee) are used.

[0257] Target element concentration = RSF (atom / cm 3 )× target element ionic strength (counts) / cured film ionic strength (counts).

[0258] (6) Long-term reliability of display devices (luminous area ratio)

[0259] According to the driving voltage shown in the table, at 10mA / cm 2 The organic EL display device was made to emit light for 250 hours, 500 hours, and 1000 hours by direct current driving, and the area of ​​the light-emitting portion at 0 hour was set as 100%, and the area ratio of the light-emitting portion at each light-emitting time (light-emitting area ratio) was measured. If the light-emitting area ratio after 250 hours, 500 hours, and 1000 hours is 80% or more, it can be said that the long-term reliability is excellent, and if it is 90% or more, it is more preferred.

[0260] [Example 1]

[0261] Under a yellow light, 37.37 g of the PGMEA solution of PIP-1 obtained in Synthesis Example 4 (8.97 g by mass of PIP-1, 28.40 g by mass of PGMEA), 0.448 g of PAG-103, 0.135 g of dibutoxyanthracene, and 10.448 g of VG-310 were weighed, and 27.00 g of GBL, 3.10 g of PGMEA, and 31.50 g of PGME (propylene glycol monomethyl ether) were added and stirred to dissolve. 0.01 g of a 5% by mass sodium chloride aqueous solution was further added, and the resulting solution was filtered using a 0.45 μmφ filter to prepare a photosensitive resin composition α-1.

[0262] Made by the following method Figure 3 The organic EL display device shown. First, after forming TFT and wiring from a power supply on a 38 mm × 46 mm alkali-free glass substrate 47, a photosensitive resin composition α-1 was applied by spin coating using a spin coater (MS-A100; manufactured by MIKASA Co., Ltd.), and then pre-baked at 100° C. for 120 seconds using a hot plate (SCW-636; manufactured by Dainippon Screen Mfg. Co., Ltd.) to prepare a pre-baked film with a film thickness of 2.0 μm.

[0263] The produced prebaked film was subjected to patterned exposure using a double-sided alignment single-sided exposure device (mask aligner PEM-6M; manufactured by Union Optical Co., LTD.) through a photomask having a predetermined pattern using an ultra-high pressure mercury lamp including all spectra corresponding to i-line, h-line and g-line, and then developed for 60 seconds using a 2.38 mass % TMAH aqueous solution using a small developing device for photolithography (AC3000; manufactured by Takizawa Sangyo Co., Ltd.), and rinsed with water for 30 seconds. The substrate was thermally cured at 250°C for 1 hour using a high-temperature inert gas oven (INH-9CD-S; manufactured by Koyo Thermo Systems Co., Ltd.) to produce a planarized film having a film thickness of about 1.0 μm.

[0264] Next, a 100 nm ITO transparent conductive film is formed by sputtering, and etching is performed in the form of a first electrode 48 to form a transparent electrode. In addition, in order to take out the second electrode, an auxiliary electrode 49 is also formed at the same time. The obtained substrate is ultrasonically cleaned for 10 minutes using Semico Clean 56 (trade name, manufactured by Furuuchi Chemical Co., Ltd.), and then washed with ultrapure water. Next, a photosensitive resin composition α-1 is applied to the entire surface of the substrate by spin coating using a spin coater (MS-A100; manufactured by MIKASA Co., Ltd.), and then pre-baked at 100°C for 120 seconds using a hot plate (SCW-636; manufactured by Dainippon Screen Mfg. Co., Ltd.) to prepare a pre-baked film with a film thickness of about 2.0 μm.

[0265] For the produced pre-baked film, a double-sided alignment single-sided exposure device (mask aligner PEM-6M; manufactured by UnionOptical Co., LTD.) was used to perform patterned exposure using an ultra-high pressure mercury lamp including the entire spectrum corresponding to the i-line, h-line and g-line through a photomask having a specified pattern, and then a small developing device for photolithography (AC3000; manufactured by TakizawaSangyo Co., Ltd.) was used to develop for 60 seconds using a 2.38 mass % TMAH aqueous solution and rinsed with water for 30 seconds. As described above, the pixel segmentation layer 50 having a shape of an opening having a width of 50 μm and a length of 260 μm and arranged at a pitch of 155 μm in the width direction and a pitch of 465 μm in the length direction, and each opening exposing the shape of the first electrode, was limited to the effective area of ​​the substrate and formed. It should be noted that the opening eventually becomes the light-emitting layer of the organic EL display device. In addition, the effective area of ​​the substrate was set to 16 mm square, and an insulating layer with an opening ratio of 18% was provided. The thickness of the insulating layer 50 was formed to be about 1.0 μm.

[0266] The obtained substrate was subjected to nitrogen plasma treatment, and then the organic EL layer 51 including the light-emitting layer was formed by vacuum deposition. It should be noted that the vacuum degree during the deposition was 1×10 -3 Pa or less, and during the evaporation, the substrate is rotated relative to the evaporation source. First, 10 nm of compound (HT-1) is evaporated as a hole injection layer, and 50 nm of compound (HT-2) is evaporated as a hole transport layer. Next, on the light-emitting layer, the compound (GH-1) as the main material and the compound (GD-1) as the dopant material are evaporated with a thickness of 40 nm in such a way that the doping concentration becomes 10%. Next, the compound (ET-1) as the electron transport material and the compound (LiQ) are stacked with a volume ratio of 1:1 and a thickness of 40 nm. The structure of the compounds used in the organic EL layer is shown below.

[0267] [Chemical formula 5]

[0268]

[0269] Next, after evaporating 2 nm of the compound (LiQ), Mg and Ag were evaporated to 100 nm at a volume ratio of 10:1 to form the second electrode 52. Finally, in a low-humidity nitrogen atmosphere, a cap-shaped glass plate was bonded using an epoxy resin adhesive to seal the substrate, and four organic EL display devices (which are quadrilaterals with one side of 5 mm) were made on one substrate. It should be noted that the film thickness here is the display value of the quartz oscillation film thickness monitor.

[0270] [Examples 2 to 14, 18]

[0271] Compositions α-2 to α-14 and α-20 were obtained in the same manner as in Example 1, with the types and amounts of the compounds being as shown in Tables 1 and 2. Organic EL display devices were produced in the same manner as in Example 1 using the obtained compositions.

[0272] [Comparative Examples 1 to 3]

[0273] An organic EL display device was produced in the same manner as in Example 1, except that the photosensitive resin compositions α-16 to α-18 described in Table 1 were used instead of the photosensitive resin composition α-1.

[0274] [Example 15]

[0275] Photosensitive resin composition α-15 was prepared in the same manner as in Example 1 except that the 5% sodium chloride aqueous solution in photosensitive resin composition α-1 was changed to a 5% potassium chloride aqueous solution. An organic EL display device was produced in the same manner as in Example 1 using the obtained photosensitive resin composition.

[0276] [Examples 16-17]

[0277] An organic EL display device was produced in the same manner as in Example 1 except that the aperture ratio of the pixel division layer was changed.

[0278] [Example 19]

[0279] Photosensitive resin composition α-21 was prepared in the same manner as in Example 1 except that the 5% sodium chloride aqueous solution in photosensitive resin composition α-1 was not added. An organic EL display device was prepared in the same manner as in Example 1 using the obtained photosensitive resin composition.

[0280] [Comparative Example 4]

[0281] Photosensitive resin composition α-19 was prepared in the same manner as in Example 1 except that the amount of 5% sodium chloride aqueous solution added in photosensitive resin composition α-1 was changed to 0.1 g. An organic EL display device was prepared in the same manner as in Example 1 using the obtained photosensitive resin composition.

[0282] The results of the evaluations of the Examples and Comparative Examples by the above methods are shown in Tables 1 and 2. The driving voltage was recorded at 10 mA / cm 2 Voltage when DC drive is performed.

[0283] Tables 1 and 2 show the compositions and evaluation results of Examples and Comparative Examples.

[0284] [Table 1-1]

[0285]

[0286] [Table 1-2]

[0287]

[0288] [Table 2-1]

[0289]

[0290] [Table 2-2]

[0291]

[0292] DESCRIPTION OF REFERENCE NUMERALS 1 TFT

[0293] 2 Wiring

[0294] 3TFT insulation layer 4Planarization layer 5ITO

[0295] 6 substrates

[0296] 7Contact holes

[0297] 8Pixel segmentation layer 9Glass substrate 10TFT

[0298] 11 Planarization layer

[0299] 12. First electrode

[0300] 13 Pre-baked film

[0301] 14 Mask 15 Active Chemical Rays

[0302] 16 pixel segmentation layer

[0303] 17 Luminous Layer

[0304] 18 second electrode

[0305] 19 Cured film for planarization 20 Cover glass

[0306] 46 Planarization layer

[0307] 47 Glass substrate

[0308] 48 first electrode

[0309] 49 auxiliary electrode

[0310] 50 pixel segmentation layer

[0311] 51 organic EL layer 52 second electrode

Claims

1. An organic EL display device comprising at least a substrate, a first electrode, a second electrode, a light-emitting layer, a planarization layer, and a pixel division layer, The planarization layer or the pixel division layer has a cured product obtained by exposing, developing, and curing the following resin composition A or resin composition B: [Resin composition A] A resin composition comprising (A-1) a resin having an alkali-soluble group protected by a protecting group that can be removed by acid (hereinafter referred to as "resin (A-1)") and (B) a photoacid generator, [Resin composition B] A resin composition comprising a resin having an alkali-soluble group, (A-2) a compound having an alkali-soluble group protected by a protecting group capable of being removed by an acid (hereinafter referred to as "compound (A-2)"), and (B) a photoacid generator, The total content of metal elements and halogen elements in the cured product measured by time-of-flight secondary ion mass spectrometry was 1.0×10 16 atom / cm 3 Above 1.0×10 23 atom / cm 3 the following.

2. The organic EL display device according to claim 1, wherein: The resin having an alkali-soluble group used in the resin composition A or the resin composition B (in which the resin before being protected by a protecting group in the resin composition A) is one or more resins selected from the group consisting of polyimide, polybenzoxazole, a polyimide precursor, a polybenzoxazole precursor and copolymers thereof.

3. The organic EL display device according to claim 1 or 2, wherein: The resin composition A further contains a compound (A-2).

4. The organic EL display device according to any one of claims 1 to 3, wherein The compound (A-2) is a phenol compound having an alkali-soluble group protected by a protecting group that can be removed by an acid, and the molecular weight before being protected by the protecting group is 100 or more and 600 or less.

5. The organic EL display device according to any one of claims 1 to 4, wherein In the resin composition A and the resin composition B, the content of the compound (A-2) is 1 part by weight or more and 30 parts by weight or less, based on 100 parts by weight of all resin components.

6. The organic EL display device according to any one of claims 1 to 5, wherein The total content of sodium and potassium in the solidified material measured by time-of-flight secondary ion mass spectrometry was 1.0×10 17 atom / cm 3 Above 1.0×10 22 atom / cm 3 the following.

7. The organic EL display device according to any one of claims 1 to 6, wherein The total content of fluorine and chlorine in the solidified material measured by time-of-flight secondary ion mass spectrometry was 1.0×10 17 atom / cm 3 Above 1.0×10 22 atom / cm 3 the following.

8. The organic EL display device according to any one of claims 1 to 7, wherein In the resin composition A and the resin composition B, the content of the photoacid generator (B) is 0.1 parts by weight or more and 30 parts by weight or less, based on 100 parts by weight of all resin components.

9. The organic EL display device according to any one of claims 1 to 8, wherein The (B) photoacid generator is one or more photoacid generators selected from the group consisting of oxime sulfonate photoacid generators, onium salt photoacid generators, and naphthalimide photoacid generators.

10. The organic EL display device according to any one of claims 1 to 9, wherein The protecting group that can be removed by acid is one or more groups selected from the group consisting of acetal groups and ketal groups.

11. The organic EL display device according to any one of claims 1 to 10, wherein: The resin composition further contains (C) a thioxanthone-based or anthracene-based sensitizer.

Citation Information

Patent Citations

  • Color filter, color paste for electronics industry, its production, pigment dispersion liquid and its production

    JP1995198928A

  • Photosensitive resin composition, cured film and organic el display device

    JP2022034533A